Active material, electrode, secondary battery, and battery pack
By using niobium-titanium composite oxides containing Nb2TiO7 phase and Nb-rich phase, combined with the regulation of potassium and phosphorus, the safety and energy density problems of lithium-ion secondary batteries during fast charging and discharging are solved, and efficient battery performance is achieved.
Patent Information
- Application Number
- CN202411712326.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2021-03-15
- Filing Date
- 2021-08-10
- Publication Date
- 2025-01-10
AI Technical Summary
Existing lithium-ion secondary batteries are prone to precipitation of metal lithium dendrites during fast charging and discharging, resulting in internal short circuits, heating or fire risks. At the same time, the energy density of titanium oxide is low, and it is difficult to reduce the electrode potential to increase capacity density.
A niobium-titanium composite oxide containing Nb2TiO7 phase and Nb-rich phase is used as the negative electrode material. The particle size distribution and crystallinity are adjusted by adding potassium and phosphorus, and the peak intensity ratio is optimized to improve the charge and discharge capacity and cycle life.
The excellent input and output characteristics and cycle life characteristics of lithium-ion secondary batteries are realized, and the lattice deformation and positive electrode deterioration during charging and discharging are reduced, and the energy density and stability of the battery are improved.
Smart Images

Figure CN119297263A_ABST
Abstract
Description
[0001] This application is a divisional application of the application with application number "202110912685.7", application date August 10, 2021, and invention name "Active material, electrode, secondary battery, battery pack and vehicle". Technical Field
[0002] Embodiments of the present invention relate to an active material, an electrode, a secondary battery, a battery pack, and a vehicle. Background Art
[0003] In recent years, as a high energy density battery, research and development of secondary batteries such as non-aqueous electrolyte batteries such as lithium ion secondary batteries has been widely carried out. Secondary batteries such as non-aqueous electrolyte secondary batteries are expected to be used as power sources for vehicles such as hybrid electric vehicles and electric vehicles, and for uninterruptible power supplies for mobile phone base stations. In addition to high energy density, secondary batteries are also required to have other excellent properties such as fast charging and discharging performance and long-term reliability. For example, secondary batteries that can be quickly charged and discharged not only greatly shorten the charging time, but also improve the power performance of vehicles such as hybrid electric vehicles and effectively recover the regenerative energy of power.
[0004] In order to enable rapid charge and discharge, it is necessary to enable electrons and lithium ions to move quickly between the positive and negative electrodes. However, if a battery using a carbon-based negative electrode is repeatedly charged and discharged quickly, dendrites of metallic lithium will form on the electrode, causing heat or fire caused by internal short circuits.
[0005] Therefore, batteries using metal composite oxides instead of carbonaceous materials in the negative electrode have been developed. Among them, batteries using titanium oxide as the negative electrode have the characteristics of being able to achieve stable rapid charge and discharge and having a longer life than batteries using carbon-based negative electrodes.
[0006] However, titanium oxide has a higher potential relative to metallic lithium than carbonaceous materials, that is, it is expensive. In addition, the capacity per unit weight of titanium oxide is low. Therefore, batteries using titanium oxide as negative electrodes have a problem of low energy density.
[0007] For example, the electrode potential of titanium oxide is about 1.5 V (vs. Li / Li + ), which is higher (more expensive) than the carbon-based negative electrode. The potential of titanium oxide is due to the fact that Ti is electrochemically inserted and released from lithium. 3+ and Ti 4+ The redox reaction between Li and Li is restricted electrochemically. + ) is a fact that lithium ions can be stably charged and discharged rapidly at a high electrode potential of about 100 Å. Therefore, it has been difficult to reduce the electrode potential in order to increase the energy density.
[0008] On the other hand, regarding the capacity per unit weight, the theoretical capacity of titanium dioxide (anatase structure) is about 165 mAh / g, and that of Li4Ti5O 12 The theoretical capacity of such spinel-type lithium-titanium composite oxide is also about 180 mAh / g. On the other hand, the theoretical capacity of ordinary graphite-based electrode materials is more than 385 mAh / g. As such, the capacity density of titanium oxide is significantly lower than that of carbon-based negative electrodes. This is because: in the crystal structure of titanium oxide, there are few sites for embedding lithium, and lithium is easily stabilized in the structure, so the actual capacity decreases.
[0009] In view of the above situation, new electrode materials containing Ti and Nb are being studied. Such niobium-titanium composite oxide materials are expected to have high charge and discharge capacities. In particular, composite oxides represented by TiNb2O7 have a high theoretical capacity of more than 380 mAh / g. Therefore, niobium-titanium composite oxides are used as a substitute for Li4Ti5O 12 However, it is difficult to intentionally reduce both fine powder and coarse crystals while maintaining high crystallinity. Therefore, there are still problems in input-output characteristics and cycle life characteristics. Summary of the invention
[0010] An object of the present invention is to provide an active material for a secondary battery that can exhibit excellent input-output characteristics and cycle life characteristics, an electrode containing the active material, a secondary battery having the electrode, a battery pack having the secondary battery, and a vehicle equipped with the battery pack.
[0011] According to the first embodiment, an active material can be provided. The active material contains a Nb2TiO7 phase and a phase selected from Nb 10 TiO 29 Phase, Nb 14 TiO 37 Phase and Nb 24 TiO 64 At least one Nb-rich phase in the phase. The active material contains potassium and phosphorus, and the total concentration of potassium and phosphorus in the active material is in the range of 0.01 mass % to 5.00 mass %. The average crystallite diameter is in the range of 80nm to 150nm. In the particle size distribution diagram obtained by laser diffraction scattering method, D10 is greater than 0.3μm and D90 is less than 10μm. The active material satisfies the peak intensity ratio expressed by the following formula (1).
[0012] 0<I B / I A ≤0.25 (1)
[0013] In formula (1), IA It is the peak intensity of the maximum peak attributable to the Nb2TiO7 phase that appears at 26.0±0.1° in the diffraction peaks obtained by wide-angle X-ray diffraction using CuKα rays as the X-ray source, B It is the peak intensity of the maximum peak attributable to the Nb-rich phase that appears at 2θ of 24.9±0.2° among the diffraction peaks.
[0014] According to the second embodiment, there is provided an electrode including the active material according to the first embodiment.
[0015] According to the third embodiment, a secondary battery including a positive electrode, a negative electrode, and an electrolyte can be provided. The negative electrode is the electrode according to the second embodiment.
[0016] According to the fourth embodiment, there is provided a battery pack including the secondary battery according to the third embodiment.
[0017] According to the fifth embodiment, there is provided a vehicle equipped with the battery pack according to the fourth embodiment.
[0018] According to the above structure, there can be provided an active material for a secondary battery that can exhibit excellent input-output characteristics and cycle life characteristics, an electrode containing the active material, a secondary battery having the electrode, a battery pack having the secondary battery, and a vehicle equipped with the battery pack. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 It is a schematic diagram showing the crystal structure of niobium titanium composite oxide Nb2TiO7.
[0020] Figure 2 It means to observe from other directions. Figure 1 Schematic diagram of the crystal structure.
[0021] Figure 3 This is a plan view schematically showing particles to be measured during observation with a transmission electron microscope (TEM).
[0022] Figure 4 It is a cross-sectional view schematically showing an example of a secondary battery according to an embodiment.
[0023] Figure 5 yes Figure 4 An enlarged cross-sectional view of portion A of the secondary battery shown.
[0024] Figure 6 It is a partially cutaway perspective view schematically showing another example of the secondary battery according to the embodiment.
[0025] Figure 7 yes Figure 6 An enlarged cross-sectional view of portion B of the secondary battery shown.
[0026] Figure 8 It is a perspective view schematically showing an example of a battery assembly according to an embodiment.
[0027] Fig. 9 It is an exploded perspective view schematically showing an example of a battery pack according to an embodiment.
[0028] Fig.10 Yes means Fig. 9 A block diagram of an example of a circuit of a battery pack is shown.
[0029] Fig.11 It is a cross-sectional view schematically showing an example of a vehicle according to the embodiment.
[0030] Fig.12 It is a diagram schematically showing another example of the vehicle according to the embodiment.
[0031] (Explanation of symbols)
[0032] 1-electrode group, 2-outer packaging member, 3-negative electrode, 3a-negative electrode collector, 3b-negative electrode active material layer, 3c-negative electrode collector portion, 4-separator, 5-positive electrode, 5a-positive electrode collector, 5b-positive electrode active material layer, 6-negative electrode terminal, 7-positive electrode terminal, 21-busbar, 22-positive electrode side lead, 23-negative electrode side lead, 24-adhesive tape, 31-storage container, 32-cover, 33-protective sheet, 34-printed circuit board, 35-wiring, 40-vehicle body, 41-vehicle power supply, 42-electric control device, 43-external terminal, 44-inverter, 45-drive motor, 100-secondary battery, 101-metal ions, 102-oxide ions, 103-skeleton structure portion, 104-gap portion, 105, 106-area domain, 200 - battery pack, 200a - battery pack, 200b - battery pack, 200c - battery pack, 300 - battery pack, 300a - battery pack, 300b - battery pack, 300c - battery pack, 301a - battery pack monitoring device, 301b - battery pack monitoring device, 301c - battery pack monitoring device, 341 - positive electrode side connector, 342 - negative electrode side connector, 343 - thermistor, 344 - protection circuit, 345 - wiring, 346 - wiring, 347 - external terminal for power supply, 348a - positive electrode side wiring, 348b - negative electrode side wiring, 400 - vehicle, 411 - battery management device, 412 - communication bus, 413 - positive electrode terminal, 414 - negative electrode terminal, 415 - switch device, L1 - connection line, L2 - connection line, W - driving wheel. DETAILED DESCRIPTION
[0033] Hereinafter, the embodiments will be described with reference to the accompanying drawings. In addition, the same symbols are used to mark the common components throughout the embodiments, and repeated descriptions are omitted. In addition, each figure is a schematic diagram for facilitating the description and understanding of the embodiments, and its shape, size, proportion, etc. are different from the actual device, but they can be appropriately changed in design by referring to the following description and known technologies.
[0034] In the past, when niobium-titanium composite oxides were produced by sintering raw materials mixed with inevitable impurities, there was a tendency to easily generate coarse grains because the melting point was lowered due to the influence of impurities. The so-called coarse grains are particles that grow with a larger primary particle size. Since coarse grains are easily broken during charge and discharge, it is difficult to form an electronic conductive path between active material particles in the active material containing coarse grains, resulting in the possibility of a decrease in rate characteristics and a decrease in cycle life characteristics. Since the coarse grains that grow due to the lowering of the melting point have high crystallinity, the Mohs hardness is also high. Therefore, for example, if the powder containing the generated coarse grains is crushed to increase the volume energy density, not only the crystallinity is reduced, but also more fine powder is generated. The specific surface area of the generated fine powder is large, which becomes a reason for the side reaction with the electrolyte during charge and discharge, thereby reducing the cycle life characteristics.
[0035] On the other hand, when sintering is performed at a lower temperature than usual in order to facilitate pulverization of the generated coarse crystal particles, the crystallinity of the particles decreases, and the number of unreacted or insufficiently reacted particles increases, thereby still causing a decrease in rate characteristics, etc. That is, it is difficult to obtain a niobium-titanium composite oxide powder having high crystallinity and a preferred particle size distribution simply by lowering the sintering temperature or pulverizing the sintered powder.
[0036] (First embodiment)
[0037] According to the first embodiment, an active material can be provided. The active material contains a Nb2TiO7 phase and a phase selected from Nb 10 TiO 29 Phase, Nb 14 TiO 37 Phase and Nb 24 TiO 64 At least one Nb-rich phase in the phase. The active material contains potassium and phosphorus, and the total concentration of potassium and phosphorus in the active material is in the range of 0.01 mass % to 5.00 mass %. The average crystallite diameter is in the range of 80nm to 150nm. In the particle size distribution diagram obtained by laser diffraction scattering method, D10 is greater than 0.3μm and D90 is less than 10μm. The active material satisfies the peak intensity ratio expressed by the following formula (1).
[0038] 0<I B / I A ≤0.25 (1)
[0039] In formula (1), I A It is the peak intensity of the maximum peak attributable to the Nb2TiO7 phase that appears at 26.0±0.1° in the diffraction peaks obtained by wide-angle X-ray diffraction using CuKα rays as the X-ray source, B It is the peak intensity of the maximum peak attributable to the Nb-rich phase that appears at 2θ of 24.9±0.2° among the diffraction peaks.
[0040] The reason why the active material according to the first embodiment can show excellent input-output characteristics and cycle life characteristics will be described.
[0041] First, the Nb2TiO7 phase will be described.
[0042] The main phase contained in the active material involved in the embodiment is a niobium titanium composite oxide phase represented by Nb2TiO7 as a representative composition. The composition of the niobium titanium composite oxide is not limited thereto, but preferably has a crystal structure that maintains the symmetry of the space group C2 / m and has the atomic coordinates described in Non-Patent Document 1 (M. Gasperin, Journal of Solid State Chemistry 53, pp144-147 (1984)).
[0043] Niobium-titanium composite oxide mainly shows a monoclinic crystal structure. As an example, Figure 1 and Figure 2 A schematic diagram of the crystal structure of monoclinic Nb2TiO7 is shown in FIG.
[0044] like Figure 1 As shown, in the crystal structure of monoclinic Nb2TiO7, metal ions 101 and oxide ions 102 constitute a skeleton structure portion 103. At the position of the metal ion 101, Nb ions and Ti ions are irregularly arranged in a ratio of Nb:Ti=2:1. The skeleton structure portion 103 is alternately arranged three-dimensionally, and there are gap portions 104 between the skeleton structure portions 103. The gap portions 104 become hosts for lithium ions. Lithium ions can be embedded in the crystal structure from 0 mol to a maximum of 5.0 mol. Therefore, the composition when 0 to 5.0 mol of lithium ions are embedded can be expressed as Li x Nb2TiO7(0≤x≤5).
[0045] Figure 1 In the example, region 105 and region 106 are portions having two-dimensional channels in the
[100] direction and the
[010] direction. Figure 2As shown in the figure, in the crystal structure of monoclinic Nb2TiO7, there is a void portion 107 in the
[001] direction. The void portion 107 has a tunnel structure that is favorable for the conduction of lithium ions, and becomes a conductive path in the
[001] direction connecting the region 105 and the region 106. The presence of this conductive path allows lithium ions to travel back and forth between the region 105 and the region 106. In addition, the niobium titanium composite oxide has a 1.5 V (relative to Li / Li + ) of lithium insertion potential. Therefore, an electrode containing a niobium-titanium composite oxide as an active material can realize a battery that can stably and repeatedly perform rapid charge and discharge.
[0046] In addition, in the above-mentioned crystal structure, when lithium ions are embedded in the voids 104, the metal ions 101 constituting the skeleton are reduced to trivalent, thereby maintaining the electrical neutrality of the crystal. In the niobium-titanium composite oxide, not only the Ti ions are reduced from tetravalent to trivalent, but also the Nb ions are reduced from pentavalent to trivalent. Therefore, the number of reduction valences per unit weight of active material is large. Therefore, even if more lithium ions are embedded, the electrical neutrality of the crystal can be maintained. Therefore, compared with compounds such as titanium oxide containing only tetravalent cations, the energy density is high. In addition, the Nb2TiO7 phase is different from the Nb2TiO7 phase described later. 10 TiO 29 Phase, Nb 14 TiO 37 Phase and Nb 24 TiO 64 Compared with the gravimetric energy density, Nb 10 TiO 29 Phase, Nb 14 TiO 37 Phase and Nb 24 TiO 64 The number of Nb atoms contained in the phase per 1 mol is large, that is, the weight per 1 mol is large.
[0047] Next, for Nb 10 TiO 29 Phase, Nb 14 TiO 37 Phase and Nb 24 TiO 64 The basic skeleton structure and Figure 1 and Figure 2 The crystal structure of monoclinic Nb2TiO7 shown is similar. When lithium ions are embedded in the voids 104, the metal ions 101 constituting the skeleton are reduced to trivalent, thereby maintaining the electrical neutrality of the crystal. 10 TiO 29 The composition of the phase can be expressed as Li x Nb 10 TiO29 (0≤x≤22). Lithium ion embedding into Nb 14 TiO 37 The composition of the phase can be expressed as Li x Nb 14 TiO 37 (0≤x≤29). Lithium ion embedding into Nb 24 TiO 64 The composition of the phase can be expressed as Li x Nb 24 TiO 64 (0≤x≤49).
[0048] In the case of Nb containing 10 TiO 29 Phase, Nb 14 TiO 37 Phase and Nb 24 TiO 64 In the Nb2TiO7 phase, the amount of Nb ions reduced from pentavalent to trivalent is greater than that in the Nb2TiO7 phase. Therefore, the number of reduced valences per 1 mole of active material is large. Therefore, even if many lithium ions are embedded, the electrical neutrality of the crystal can be maintained. Therefore, the Nb 10 TiO 29 Phase, Nb 14 TiO 37 Phase and Nb 24 TiO 64 At least one Nb-rich phase in the phase can stably maintain the crystal structure even when lithium ions are excessively embedded in it, compared with the Nb2TiO7 phase. Therefore, even if lithium ions are excessively embedded in the Nb-rich phase, the active material particles can be stably charged and discharged. That is, the overcharge resistance of the Nb-rich phase is excellent. In addition, the so-called Nb-rich phase in this specification means a niobium-titanium composite oxide phase with a Nb / Ti ratio greater than 2. The active material involved in the embodiment may be a niobium-titanium composite oxide containing a Nb2TiO7 phase and a Nb-rich phase.
[0049] On the other hand, the Nb-rich phase has a smaller reduction valence per unit active material weight than the Nb2TiO7 phase. That is, the Nb-rich phase has a larger weight per mol and therefore has a lower weight energy density than the Nb2TiO7 phase.
[0050] If the active material contains not only the Nb2TiO7 phase but also a phase selected from Nb 10 TiO 29 Phase, Nb 14 TiO 37 Phase and Nb 24 TiO 64At least one Nb-rich phase is present in the positive electrode, and when the secondary battery reaches an overcharge state, the potential of the Nb-rich phase decreases preferentially. Therefore, during charging, a certain charging voltage can be ensured while suppressing the potential rise of the positive electrode. As a result, the active material involved in the embodiment can suppress the generation of oxidizing gas in the positive electrode and the degradation of the positive electrode, and thus has excellent cycle life characteristics.
[0051] In addition, the Nb-rich phase can alleviate the lattice deformation caused by the insertion and extraction of Li during charge and discharge. This is because the combination of oxide ions and Nb ions constituting the skeleton is enhanced. Therefore, the deformation of the lattice during Li charge and discharge can be suppressed, and the cycle life characteristics are excellent.
[0052] In order to obtain the above advantages, it is effective that the active material contains a predetermined amount of Nb-rich phase. The predetermined amount is a quantity that satisfies the peak intensity ratio (I B / I A ) of formula 1. However, in the active material containing the Nb-rich phase, as mentioned above, the combination of oxide ions and Nb ions constituting the skeleton is enhanced, and more particles with high hardness are generated. As a result, there are more particles with a large particle size in the active material, and D90 is large, so it is difficult to obtain high input-output characteristics. In addition, if D90 is reduced by crushing the hard particles, the crystallinity decreases and the cycle life characteristics decrease. Therefore, in the active material containing the Nb-rich phase, it is difficult to take into account both high input-output characteristics and cycle life.
[0053] The active material involved in the embodiment contains potassium (K) and phosphorus (P). At least one of potassium and phosphorus is preferably present at the particle interface of the active material particles. Potassium and phosphorus exist as oxides, for example. A portion of potassium and a portion of phosphorus can also enter the crystalline phase. Potassium has the effect of lowering the melting point of the active material, and high crystallinity can be obtained at a relatively low sintering temperature. On the other hand, by the presence of phosphorus in at least a portion of the surface of the active material particles, it has the effect of inhibiting particle growth and preventing the active material particles from coarsening due to necking. By the coexistence of potassium and phosphorus in the active material, D90 can be reduced and D10 can be increased even in an active material containing a Nb-rich phase, and high crystallinity can be obtained at the same time, resulting in both high input-output characteristics and cycle life.
[0054] The total concentration of potassium and phosphorus in the active material is in the range of 0.01 mass % or more and 5.00 mass % or less. When the concentration is less than 0.01 mass %, the above effect cannot be obtained. When the concentration exceeds 5.00 mass %, the battery capacity decreases because the site where Li should be embedded is occupied by potassium, or the phosphorus-containing oxide becomes a resistance component on the particle interface and reduces the input-output characteristics. The total concentration of potassium and phosphorus in the active material is preferably in the range of 0.020 mass % or more and 4.00 mass % or less, and more preferably in the range of 0.050 mass % or more and 2.50 mass % or less. The total concentration of potassium and phosphorus in the active material may also be in the range of more than 0.200 mass % and 5.00 mass % or less.
[0055] The potassium concentration (hereinafter also referred to as "C K ”) is, for example, in the range of 0.005 mass % to 5.00 mass %, preferably in the range of 0.01 mass % to 0.2 mass %. If the potassium concentration C K If the concentration is too high, the battery capacity may be reduced due to potassium occupying the sites where Li should be inserted. Alternatively, the flux effect of potassium may cause abnormal growth of particles, which may prevent smooth insertion and extraction of Li, and may reduce the input-output characteristics.
[0056] The phosphorus concentration (hereinafter also referred to as “C P ”) is, for example, in the range of 0.001 mass % to 1.00 mass %, preferably in the range of 0.005 mass % to 0.05 mass %. If the phosphorus concentration C P If it is too high, the phosphorus-containing oxide becomes a resistance component at the particle interface, and there is a possibility that the input-output characteristics will deteriorate.
[0057] Potassium concentration in active substance C K and the phosphorus concentration C in the active material P The ratio (C K / C P ) is, for example, in the range of 1.0 to 50.0, preferably in the range of 2.0 to 20.0. K / C P ) may also be in the range of 2.0 to 50.0, or in the range of 5.0 to 40.0. In the active material involved in the embodiment, the potassium concentration is preferably higher than the phosphorus concentration. Because phosphorus has a strong tendency to remain on the surface of the particles, although it has the function of inhibiting the necking and abnormal growth of the particles, if the phosphorus concentration is higher than the potassium concentration, sufficient crystal growth cannot be promoted, and the phosphorus remaining on the surface of the active material hinders the movement of Li ions. Therefore, for example, the input-output characteristics are reduced.
[0058] In the particle size distribution diagram obtained by the laser diffraction scattering method for the active material involved in the embodiment, the volume frequency 10% (D10) is above 0.3μm. A high value of D10 means less fine powder. When D10 is above 0.3μm, there is less fine powder contained in the active material, so the side reaction with the electrolyte can be reduced. As a result, a secondary battery showing excellent rate characteristics and cycle life characteristics can be achieved. D10 is preferably in the range of 0.4μm to 1.5μm, and more preferably in the range of 0.5μm to 1.0μm. If D10 is greater than 1.5μm, there is a tendency for rapid charge and discharge performance to decrease.
[0059] In addition, in the particle size distribution diagram, the volume frequency 90% (D90) is less than 10 μm. A low value of D90 means that there are fewer coarse particles. When D90 is less than 10 μm, there are fewer coarse particles contained in the active material, so it is difficult to produce the breakage of the coarse particles accompanying charging and discharging. Because the coarse particles are not broken, it is easy to maintain a good electronic conductive path, and it is also possible to reduce side reactions caused by the increase in specific surface area. Therefore, excellent rate characteristics and cycle life characteristics can be achieved. According to an example, D90 is 5.0 μm or more. D90 is preferably in the range of 6.0 μm to 9.0 μm.
[0060] In the past, in order to make D90 below 10μm, it was necessary to lower the sintering temperature or subject the sintered powder to strong crushing. Therefore, it is difficult to reduce D90 while increasing D10 while maintaining high crystallinity. However, since the active material involved in the embodiment contains potassium and phosphorus at a specified concentration, it is possible to improve crystallinity during the annealing stage when the active material is synthesized, while suppressing the necking of the particles. Thus, by suppressing grain growth during annealing, not only the number of coarse grains is reduced, but also the particles are prone to collapse even if the crushing after annealing is mild. Therefore, coarse grains can be crushed without reducing the crystallinity of the active material, thereby reducing D90. In addition, the occurrence of fine powder can also be suppressed in the crushing under mild conditions. That is, D10 can be increased. Thus, even if the Nb-rich phase with high hardness of the active material particles coexists, a preferred particle size distribution can be obtained without strong crushing.
[0061] The average crystallite size of the active material is, for example, in the range of 80 nm to 150 nm, preferably in the range of 90 nm to 150 nm, and more preferably in the range of 95 nm to 120 nm. The average crystallite size is 80 nm or more, which means that the crystal structure is firmly formed. Such a crystal structure is difficult to deteriorate even with repeated rapid charge and discharge, so it helps to improve the life performance of the secondary battery. If the average particle size is greater than 150 nm, the diffusion distance of the Li ions is extended, and there is a possibility that the mobility of the Li ions in rapid charge and discharge is reduced.
[0062] Furthermore, the active material according to the embodiment satisfies the peak intensity ratio represented by the following formula (1).
[0063] 0<I B / I A ≤0.25 (1)
[0064] In formula (1), I A It is the peak intensity of the maximum peak attributable to the Nb2TiO7 phase that appears at 26.0±0.1° in the diffraction peaks obtained by wide-angle X-ray diffraction using CuKα rays as the X-ray source. B In the above diffraction peak, the peak at 2θ of 24.9±0.2° belongs to Nb 10 TiO 29 Phase, Nb 14 TiO 37 Phase and Nb 24 TiO 64 The peak intensity of the maximum peak of at least one Nb-rich phase in the phase. The method for implementing the wide-angle X-ray diffraction method will be described later.
[0065] Peak intensity I A It is the peak intensity (peak height) attributed to the Nb2TiO7 phase. This peak has the maximum peak intensity in the range of 2θ of 26.0±0.1°. Peak intensity I A Large means that the weight of the Nb2TiO7 phase in the active material is large.
[0066] Peak intensity I B is attributed to the selected Nb 10 TiO 29 Phase, Nb 14 TiO 37 Phase and Nb 24 TiO 64 The peak intensity (peak height) of at least one Nb-rich phase in the phase. This peak is the peak with the maximum peak intensity within the range of 2θ of 24.9±0.2°. Peak intensity I B Large means that the weight of the Nb-rich phase in the active material is large.
[0067] As described above, the active material contains a Nb-rich phase to improve overcharge resistance, thereby improving the life characteristics of the secondary battery. However, when the Nb-rich phase is infinitely increased, the overcharge resistance is not improved in accordance with the increase. In addition, if the peak intensity is greater than I B / I A If it is too large, not only the weight energy density will decrease due to the increase in the weight of the active material, but also the Nb2TiO7 phase and the Nb 10 TiO 29 Phase, Nb 14 TiO37 Phase and Nb 24 TiO 64 The difference in volume expansion rate of at least one Nb-rich phase during charge and discharge may cause deformation of the electrode or cracking of the active material particles, which is not preferred. B / I A ) is less than 0.25.
[0068] Peak intensity ratio I B / I A It is better to be greater than 0, but if the peak intensity is greater than I B / I A If it is too small, the weight of the Nb-rich phase will be insufficient, and the overcharge resistance and cycle life will tend to decrease.
[0069] Peak intensity ratio I B / I A It is preferably 0.005 or more and 0.20 or less, more preferably 0.01 or more and 0.15 or less, and further preferably 0.05 or more and 0.1 or less.
[0070] The active material involved in the embodiment may further contain at least one additional element selected from Si, Fe, Ta, Na, Y, Al and Sn. The amount of the additional element contained in the active material is preferably 0.5 atm% or less relative to the Nb element in the active material. When the active material contains at least one selected from Fe, Ta, Y, Al and Sn, the electronic conductivity of the active material can be improved. When the active material contains at least one selected from Si and Na, the capacity reduction caused by the heavy Nb-rich phase can be reduced.
[0071] Regarding the above-mentioned additional elements, the Nb2TiO7 phase may also contain Nb 10 TiO 29 Phase, Nb 14 TiO 37 Phase and Nb 24 TiO 64 At least one Nb-rich phase in the phase may also contain an additive element. Alternatively, both the Nb2TiO7 phase and the Nb-rich phase may contain additive elements. However, in either case, the content of the additive element is preferably less than 0.5 atm% relative to the Nb element in the active material.
[0072] The crystal structure of the active material particles can be observed, for example, by powder X-ray diffraction measurement and transmission electron microscope (TEM) observation, etc. The details of these measurement methods will be described later.
[0073] Next, the morphology and specific surface area of the active material according to the embodiment will be described.
[0074] <Form>
[0075] The form of the active material (niobium titanium composite oxide) involved in the embodiment is not particularly limited. The active material can be, for example, in the form of primary particles containing Nb2TiO7 phase, Nb-rich phase, potassium and phosphorus. Alternatively, the active material can be a plurality of particles formed by a mixture of primary particles consisting of a single phase of Nb2TiO7 phase and primary particles consisting of a single phase of Nb-rich phase, or a plurality of particles containing potassium and phosphorus in at least a portion of these particles. The above-mentioned primary particles can also be condensed to form a secondary particle form. The particles of the niobium titanium composite oxide can also be a mixture of primary particles and secondary particles.
[0076] The particles of the niobium-titanium composite oxide may also have a carbon-containing layer on the surface. The carbon-containing layer may be attached to the surface of the primary particle or to the surface of the secondary particle. Alternatively, the particles of the niobium-titanium composite oxide may also include secondary particles formed by agglomeration of primary particles having a carbon-containing layer attached to the surface. Such secondary particles have carbon between the primary particles and can thus exhibit excellent electrical conductivity. A morphology containing such secondary particles is preferred because the active material layer can exhibit lower resistance.
[0077] <Specific surface area>
[0078] The specific surface area of the active material according to the embodiment is not particularly limited, but is preferably 0.5 m 2 / g or more and 5m 2 / g or less. As long as the specific surface area is 0.5m 2 / g or more, the contact area with the electrolyte can be ensured, good discharge rate characteristics can be easily obtained, and the charging time can be shortened. On the other hand, as long as the specific surface area is 5m 2 / g or less, the reactivity with the electrolyte will not be excessively increased, and the life characteristics can be improved. In addition, the coating properties of the slurry containing the active material used for electrode production described later can be improved.
[0079] Here, the specific surface area is determined by adsorbing molecules with known adsorption area onto the surface of powder particles at the temperature of liquid nitrogen, and calculating the specific surface area of the sample from the amount of adsorption. The most commonly used method is the BET method, which uses low-temperature and low-humidity physical adsorption of inert gases. It is the most famous theory as a method for calculating specific surface area by expanding the monolayer adsorption theory, namely the Langmuir theory, to multi-molecular layer adsorption. The specific surface area calculated by this method is called the BET (Brunauer, Emmett, Teller) specific surface area.
[0080] <Method for producing active material>
[0081] The active material according to the embodiment can be produced, for example, by the synthesis method described below.
[0082] First, the starting materials are mixed. As the starting materials containing niobium and titanium, oxides or salts containing Nb and Ti are prepared. For example, Nb2O5 particles and TiO2 particles can be used as the starting materials. The molar ratio of niobium to titanium (M) is set according to the composition of the target Nb-rich phase. Nb / M Ti ) is mixed in a manner such that the starting materials have a range of 2.0 or more and 4.0 or less. Nb " represents the mass (number of moles) of niobium atoms contained in the niobium-titanium composite oxide, "M Ti ” represents the amount (number of moles) of titanium atoms contained in the niobium-titanium composite oxide. In the present specification, “the molar ratio of niobium to titanium (M Nb / M Ti )" is recorded as "Nb / Ti ratio".
[0083] After the raw materials are mixed, the obtained mixture is crushed to obtain a mixture that is as uniform as possible. Next, the obtained mixture is subjected to temporary calcination (first calcination). The temporary calcination is performed at a temperature range of 500 to 900° C. for a total of 10 to 40 hours in two or more steps. In this way, highly uniform precursor particles can be obtained.
[0084] Next, the obtained precursor particles are subjected to formal calcination (second calcination). The formal calcination is carried out at a temperature below 800°C to 1000°C for 1 hour to 10 hours. During this time, it is best to determine the calcination time in a manner that gives priority to obtaining the desired particle size distribution. It is best that the particles obtained by the formal calcination have a low crystallinity state. In this way, by implementing relatively low temperature and multiple calcinations from temporary calcination to formal calcination, the generation of coarse particles and fine particles can be suppressed.
[0085] Next, an oxide or salt containing potassium and phosphorus is prepared. With respect to the previously obtained particles after formal firing, the oxide or salt is added in a manner such that the potassium and phosphorus content is within a range of 0.010 mass % or more and 5.00 mass % or less, and wet mixing is performed. At this time, if a raw material soluble in a solvent such as water is used to wet mix the supply source containing potassium and phosphorus, it can be evenly distributed on the surface of the fired particles, so it is preferred.
[0086] Next, the mixture of the sintered particles obtained by wet mixing and potassium and phosphorus is subjected to annealing. The annealing is preferably carried out at a temperature of 800°C to 900°C for 1 to 10 hours. The flux effect of potassium and phosphorus can suppress grain growth and improve crystallinity. Without applying strong shear force as much as possible, the powder obtained in this way is subjected to gentle pulverization for as short a time as possible. In this pulverization, for example, a roller compactor, a bead mill device, a ball mill device, etc. can be used. Thus, the crystallinity can be improved without causing a significant change in the particle size distribution obtained by formal sintering.
[0087] In addition, by changing the pulverization conditions after the above annealing, the D10, D50 and D90 of the obtained active material can be controlled. For example, there is a tendency that D10, D50 and D90 can be reduced by extending the pulverization time. In addition, for example, there is a tendency that D10, D50 and D90 can be reduced by using a medium with a smaller diameter as a pulverization medium. Alternatively, by subjecting the powder to centrifugal separation, small particles of D10 can be captured, or large particles of D90 can be captured. For example, by mixing the captured particles with an active material synthesized separately, D10, D50 and D90 can be controlled.
[0088] As described above, when manufacturing a niobium-titanium composite oxide having a Nb2TiO7 phase and a Nb-rich phase, potassium and phosphorus are added to the calcined particles so as to achieve a desired particle size distribution, and then annealing is performed, and then mild pulverization is performed to obtain an active material powder having high crystallinity and a small proportion of fine powder. Thus, by suppressing the deformation of the lattice during Li charge and discharge, an active material that improves cycle life characteristics and shows excellent input-output characteristics can be obtained.
[0089] Furthermore, the niobium-titanium composite oxide synthesized by the above method can also absorb lithium ions by charging after assembling a battery. Alternatively, it can be synthesized as a lithium-containing composite oxide by using a lithium-containing compound such as lithium carbonate as a starting material.
[0090] <Powder X-ray diffraction measurement of active material and peak intensity ratio I B / I A Calculation>
[0091] The powder X-ray diffraction measurement of the active material can be performed, for example, as follows.
[0092] First, crush the sample to an average particle size of about 5 μm. Fill the crushed sample into a retainer portion with a depth of 0.2 mm formed on the glass sample plate. At this time, be careful to ensure that the sample is fully filled into the retainer portion. In addition, in order to avoid cracks, gaps, etc., be careful not to fill the sample excessively or insufficiently. Next, press another glass plate from the outside to smooth the surface of the sample filled in the retainer portion. Be careful not to create unevenness relative to the reference surface of the retainer due to excessive or insufficient filling.
[0093] Next, the glass plate filled with the sample is placed on a powder X-ray diffraction device, and a diffraction pattern (XRD pattern: X-ray diffraction pattern) is obtained using Cu—Kα rays.
[0094] In addition, depending on the particle shape of the sample, the orientation of the particles sometimes becomes larger. When the orientation of the sample is high, there is a possibility that the position of the peak will shift or the intensity ratio will change depending on the filling method of the sample. A glass capillary is used to measure such a sample with a significantly high orientation. Specifically, the sample is inserted into the capillary, and the capillary is placed on a rotating sample stand for measurement. Orientation can be relaxed by such a measurement method. As a glass capillary, a Lindemann glass capillary with a diameter of 1 mm to 6 mm Φ is preferably used.
[0095] When the active material contained in the electrode is subjected to powder X-ray diffraction measurement, the measurement can be performed, for example, as follows.
[0096] First, in order to grasp the crystal state of the active material, the lithium ions are completely separated from the active material. For example, when the active material is used for the negative electrode, the battery is completely discharged. For example, the battery can be discharged by repeatedly discharging the battery at 0.1C current in a 25°C environment until the rated end voltage or the battery voltage reaches 1.0V, so that the current value during discharge is less than 1 / 100 of the rated capacity. Even in the discharge state, there are sometimes residual lithium ions.
[0097] Next, the battery is disassembled in a glove box filled with argon, the electrodes are taken out, and cleaned with a suitable solvent. As a suitable solvent, for example, ethyl methyl carbonate can be used. If the cleaning of the electrode is insufficient, impurity phases such as lithium carbonate and lithium fluoride are sometimes mixed in due to the influence of the residual lithium ions in the electrode. In this case, it is best to use an airtight container in which the atmosphere is measured in an inert gas. The cleaned electrode is cut into an area equal to the area of the holder of the powder X-ray diffraction device as a measurement sample. The sample is directly attached to the glass holder for measurement.
[0098] At this time, the peaks originating from the current collector, i.e., metal foil, conductive agent, and adhesive, are grasped by measuring in advance using XRD. Of course, if these are grasped in advance, the operation can also be omitted. When the peak of the current collector overlaps with the peak of the active material, it is preferably measured after the active material-containing layer is peeled off from the current collector. This is to separate the overlapping peaks when the peak intensity is quantitatively measured. The active material-containing layer can also be peeled off by a physical method, but it is easy to peel off if ultrasound is applied in a solvent. When ultrasonic treatment is performed to peel off the active material-containing layer from the current collector, the electrode body powder (including active material, conductive agent, and adhesive) can be recovered by volatilizing the solvent. By filling the recovered electrode body powder in, for example, a Lindemann glass capillary and measuring it, powder X-ray diffraction measurement of the active material can be performed. Furthermore, the electrode body powder recovered by ultrasonic treatment can also be provided for various analyses other than powder X-ray diffraction measurement.
[0099] As an apparatus for powder X-ray diffraction measurement, for example, SmartLab manufactured by Rigaku Corporation is used. The measurement conditions are defined as follows:
[0100] X-ray source: Cu target
[0101] Power: 45kV 200mA
[0102] Sola slit: Both incident and received light are 5°
[0103] Step amplitude (2θ): 0.02deg
[0104] Scanning speed: 20 degrees per minute
[0105] Semiconductor detector: D / teX Ultra 250
[0106] Measuring range: 5°≤2θ≤90°
[0107] Sample plate holder: Flat glass sample plate holder (thickness 0.5 mm).
[0108] When other devices are used, in order to obtain measurement results equivalent to those described above, measurement is performed using standard Si powder for powder X-ray diffraction, and the peak intensity and peak top position are adjusted under the same conditions as those of the above device.
[0109] In the obtained diffraction pattern, the peak intensity I of the peak belonging to the Nb2TiO7 phase having the maximum peak intensity in the range of 2θ of 26.0±0.1° was determined. A In addition, among the diffraction peaks, the peak with the largest peak intensity in the range of 2θ of 24.9±0.2° and the peak attributable to Nb 10 TiO 29 Phase, Nb14 TiO 37 Phase and Nb 24 TiO 64 The peak intensity I of at least one Nb-rich phase in the phase B Then, calculate the peak intensity ratio I B / I A .
[0110] <Confirmation of crystallite size>
[0111] The XRD diffraction pattern obtained by powder X-ray diffraction must be able to be used for Rietveld analysis. To collect data for Rietveld, the measurement time and / or X-ray intensity should be appropriately adjusted so that the step width reaches 1 / 3 to 1 / 5 of the minimum half-value width of the diffraction peak and the intensity at the peak position of the strongest reflection reaches 5,000 to 10,000 counts.
[0112] The obtained XRD pattern is analyzed by the Rietveld method. In the Rietveld method, the diffraction pattern is calculated by a pre-estimated crystal structure model. By fully fitting the calculated value with the measured value, the parameters (lattice constant, atomic coordinates, occupancy, etc.) related to the crystal structure can be accurately analyzed. Thus, the characteristics of the crystal structure of the synthesized oxide can be investigated. In addition, the occupancy in each site of the constituent elements can also be investigated.
[0113] The fitting parameter S is used as a measure for estimating the degree of agreement between the observed intensity and the calculated intensity in the Rietveld analysis. The analysis needs to be performed in such a way that S is less than 1.8. In addition, when determining the occupancy of each site, the standard deviation σ must be taken into account. j About the fitting parameter S and standard deviation σ defined here j , it is stipulated that the mathematical formula described in non-patent document 2 (compiled by Izumi Nakai et al.: "The Reality of Powder X-ray Diffraction", first edition, Asakura Bookstore, February 10, 2002, pages 97 to 115) is used for inference. In this method, for the monoclinic niobium-titanium composite oxide having the symmetry of the space group C2 / m of the embodiment, the case of fitting when assuming that each cation is equally occupied at each metal cation occupied site of 2a or 4i in the crystal structure, and the case of fitting by setting individual occupancy rates for each element assuming that each cation exists unevenly. As a result, it can be judged that the side with a smaller convergence value of the fitting parameter S, that is, the side with better fitting, is close to the actual occupancy state. Therefore, it can be judged whether each cation is arranged irregularly.
[0114] In order to determine the crystallite size, the diffraction line with the strongest diffraction intensity is selected. x Ti1-y M1 y Nb 2-z M2 z O 7+δ In the compound represented by, the peak of the (110) plane is measured. Here, M1 is at least one selected from Zr, Si and Sn. M2 is at least one selected from V, Ta, Bi, K, Ca, B, Co, Fe, Mn, Ni, Si, P and Mo. The subscripts in the composition formula are 0≤x≤5, 0≤y<1, 0≤z<2, -0.3≤δ≤0.3. The crystallite size can be calculated from the half-value width of the obtained peak. Here, the crystallite size is calculated from the Scherrer formula shown in the following formula 2.
[0115]
[0116] Here, K = 0.9, λ = 0.15406 nm, β e : Half-value width of diffraction peak, β o : Correction value of half-value width (0.07°).
[0117] <High-frequency inductively coupled plasma optical emission spectrometry>
[0118] The concentrations of potassium and phosphorus in the active material can be analyzed by high-frequency inductively coupled plasma (ICP: Inductively Coupled Plazma) emission spectrometry.
[0119] After a portion of the active material powder is placed in an appropriate solvent, it is irradiated with ultrasound. For example, the electrode body is placed in ethyl methyl carbonate added to a glass beaker, and it is vibrated in an ultrasonic cleaning machine, thereby being able to peel off the active material layer from the collector. Next, the peeled active material layer is dried by reduced pressure drying. The obtained active material layer is crushed with a mortar, etc. to form a powder containing an active material, a conductive agent, a binder, etc. By dissolving the powder with an acid, a liquid sample containing an active material can be prepared. At this time, hydrochloric acid, nitric acid, sulfuric acid, hydrogen fluoride, etc. can be used as an acid. By subjecting the liquid sample to ICP emission spectrometry, the concentrations of potassium and phosphorus contained in the active material can be analyzed respectively.
[0120] <TEM observation of active substances>
[0121] By observing with a transmission electron microscope (TEM), the distribution of each crystalline phase can be confirmed. In addition, the presence of potassium and phosphorus as added elements at the particle interface can be confirmed. Energy dispersive X-ray spectroscopy (EDX) can also be implemented as needed.
[0122] When observing under a transmission electron microscope, it is preferred to bury the sample powder as the object in a resin, etc., and cut out the inside of the test body by mechanical grinding and ion milling. In addition, the same treatment can be performed even if the sample as the object is an electrode body. For example, the electrode body can be buried in the resin in its original state, and the desired place can be observed. It can also be observed as an electrode powder in which the collector (metal foil) is peeled off from the electrode body and a conductive material and an adhesive are mixed. In this way, it is possible to understand how the two crystalline phases are distributed in the primary particle, and it is possible to understand the inclination of the composition within the particle.
[0123] The following reference Figure 3 A specific example will be described. Figure 3 It is a plan view schematically showing the particle to be measured. First, the centroid of the particle to be measured is regarded as the center of the particle. Next, five measuring points are set at equal intervals on a straight line connecting the center of the particle and an arbitrary point on the surface of the particle. The multi-wave interference image of the particle portion at three points in the area orthogonal to each measuring point is investigated, and the electron beam diffraction pattern is observed. This observation can be used to understand the crystal structure contained in the measuring point. For example, by simulating the electron beam diffraction pattern in advance, it is easy to distinguish between Nb2TiO7 phase and Nb 10 TiO 29 Phase, Nb 14 TiO 37 Phase and Nb 24 TiO 64 Phase and phases beyond it.
[0124] <Measurement of Particle Size Distribution of Active Material Particles by Laser Diffraction Scattering Method>
[0125] The electrode body powder described in the above-mentioned powder X-ray diffraction measurement item is sintered to burn off the conductive agent and the binder. The remaining active material particles are dispersed in N-methyl-2-pyrrolidone (NMP) solvent and ultrasonically treated to obtain a dispersed solution as a sample for particle size distribution measurement. The dispersed solution is subjected to a particle size distribution measurement of the constituent particles using a laser diffraction distribution measurement device. As a measurement device, for example, Microtrac MT3100II manufactured by Microtrac BEL Co., Ltd. can be used.
[0126] The ultrasonic treatment when obtaining the above-mentioned dispersion solvent is performed by a sample supply system attached to the laser diffraction distribution measuring device. The ultrasonic treatment is performed at a power of 40 W for 300 seconds, for example.
[0127] According to the first embodiment, an active material can be provided. The active material contains a Nb2TiO7 phase and a phase selected from Nb 10 TiO29 Phase, Nb 14 TiO 37 Phase and Nb 24 TiO 64 At least one Nb-rich phase in the phase. The active material contains potassium and phosphorus, and the total concentration of potassium and phosphorus in the active material is in the range of 0.01 mass % to 5.00 mass %. The average particle size is in the range of 80nm to 150nm. In the particle size distribution diagram obtained by laser diffraction scattering method, D10 is greater than 0.3μm and D90 is less than 10μm. The active material satisfies the peak intensity ratio expressed by the following formula (1).
[0128] 0<I B / I A ≤0.25 (1)
[0129] In formula (1), I A It is the peak intensity of the maximum peak attributable to the Nb2TiO7 phase that appears at 26.0±0.1° in the diffraction peaks obtained by wide-angle X-ray diffraction using CuKα rays as the X-ray source. B It is the peak intensity of the maximum peak attributable to the Nb-rich phase that appears at 2θ of 24.9±0.2° among the diffraction peaks.
[0130] The active material according to the embodiment can realize a secondary battery that can exhibit excellent input-output characteristics and cycle life characteristics.
[0131] (Second embodiment)
[0132] According to a second embodiment, an electrode is provided.
[0133] The electrode involved in the second embodiment contains the active material involved in the first embodiment. The electrode involved in the embodiment may be a negative electrode or a positive electrode. The electrode involved in the embodiment is, for example, an electrode for a battery, an electrode for a secondary battery, or an electrode for a lithium secondary battery. The electrode may be a negative electrode containing the active material involved in the first embodiment as a negative electrode material.
[0134] The electrode according to the second embodiment may include a current collector and an active material-containing layer. The active material-containing layer may be formed on one side or both sides of the current collector. The active material-containing layer may include an active material and any conductive agent and binder.
[0135] The active material-containing layer may contain the active material according to the first embodiment alone, or may contain two or more active materials according to the first embodiment. In addition, it may contain a mixture of one or more active materials according to the first embodiment and one or more other active materials.
[0136] As examples of other active materials, lithium titanate having a ramsdellite structure (e.g., Li 2+y Ti3O7, 0≤y≤3), lithium titanate with spinel structure (such as Li 4+x Ti5O 12 , 0≤x≤3), titanium dioxide (TiO2), niobium pentoxide (Nb2O5), anatase titanium dioxide, rutile titanium dioxide, pyrolusite titanium composite oxide and orthorhombic titanium-containing composite oxide. As an example of other active materials, a niobium titanium composite oxide different from the active material involved in the first embodiment may be further contained. The niobium titanium composite oxide may have a monoclinic crystal structure.
[0137] Examples of orthorhombic titanium-containing composite oxides include Li 2+a M(I) 2-b Ti 6-c M(II) d O 14+σ Compound represented by. Here, M(I) is at least one selected from Sr, Ba, Ca, Mg, Na, Cs, Rb and K. M(II) is at least one selected from Zr, Sn, V, Nb, Ta, Mo, W, Y, Fe, Co, Cr, Mn, Ni and Al. The subscripts in the composition formula are 0≤a≤6, 0≤b<2, 0≤c<6, 0≤d<6, -0.5≤σ≤0.5. As specific examples of orthorhombic titanium-containing composite oxides, Li 2+a Na2Ti6O 14 (0≤a≤6).
[0138] Examples of the monoclinic niobium titanium composite oxide include Li x Ti 1-y M1 y Nb 2-z M2 z O 7+δ Here, M1 is at least one selected from Zr, Si and Sn. M2 is at least one selected from V, Ta and Bi. The subscripts in the composition formula are 0≤x≤5, 0≤y<1, 0≤z<2, -0.3≤δ≤0.3. As specific examples of monoclinic niobium titanium composite oxides, Li x Nb2TiO7(0≤x≤5).
[0139] As other examples of monoclinic niobium titanium composite oxides, Ti 1-y M3 y+z Nb 2-z O 7-δHere, M3 is at least one selected from Mg, Fe, Ni, Co, W, Ta and Mo. Each subscript in the composition formula is 0≤y<1, 0≤z≤2, -0.3≤δ≤0.3.
[0140] Conductive agents are added to improve current collection performance and to suppress the contact resistance between the active material and the current collector. Examples of conductive agents include carbon black such as vapor grown carbon fiber (VGCF), acetylene black, and carbonaceous materials such as graphite. One of these can be used as a conductive agent, or two or more of them can be combined and used as a conductive agent. Alternatively, instead of using a conductive agent, carbon coating or an electronically conductive inorganic material coating can be applied to the surface of the active material particles.
[0141] The binder is used to fill the gaps between the dispersed active materials and to bind the active materials to the current collector. Examples of binders include polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVdF), fluorine rubber, styrene-butadiene rubber, polyacrylic acid compounds, imide compounds, carboxymethyl cellulose (CMC) and salts of CMC. One of these can be used as a binder, or two or more of them can be used in combination as a binder.
[0142] The proportion of active material, conductive agent and binder in the active material layer can be changed appropriately according to the purpose of the electrode. For example, when the electrode is used as the negative electrode of a secondary battery, it is preferred to mix active material, conductive agent and binder in a ratio of 68% by mass or more and 96% by mass or less, 2% by mass or more and 30% by mass or less, and 2% by mass or more and 30% by mass or less. By setting the amount of conductive agent to more than 2% by mass, the current collection performance of the active material layer can be improved. In addition, by setting the amount of binder to more than 2% by mass, the binding property of the active material layer and the collector can be made sufficient, and excellent cycle performance can be expected. On the other hand, conductive agent and binder are preferably set to less than 30% by mass in terms of seeking high capacity.
[0143] As the current collector, a material that is electrochemically stable at the potential of embedding and de-embedding lithium (Li) in the active material can be used. For example, when using the active material as the negative electrode material, the current collector is preferably made of copper, nickel, stainless steel or aluminum, or an aluminum alloy containing one or more elements selected from Mg, Ti, Zn, Mn, Fe, Cu and Si. The thickness of the current collector is preferably 5 μm or more and 20 μm or less. A current collector with such a thickness can achieve a balance between the strength and lightness of the electrode.
[0144] Furthermore, the current collector may include a portion on the surface of which the active material-containing layer is not formed. This portion may function as a current collector tab.
[0145] The electrode can be made, for example, by the following method. First, the active material, conductive agent and binder involved in the embodiment are suspended in a solvent to prepare a slurry. The slurry is applied to one or both sides of the collector. Next, the applied slurry is dried to obtain a laminate containing an active material layer and a collector. Then, the laminate is pressurized. In this way, an electrode is made.
[0146] Alternatively, the electrode can also be made by the following method. First, the active material, the conductive agent and the binder are mixed to obtain a mixture. Then, the mixture is formed into particles. Then, the particles are arranged on a current collector to obtain an electrode.
[0147] The electrode according to the second embodiment contains the active material according to the first embodiment. Therefore, the electrode can realize a secondary battery that can exhibit excellent input-output characteristics and cycle life characteristics.
[0148] (Third embodiment)
[0149] According to the third embodiment, a secondary battery including a negative electrode, a positive electrode and an electrolyte is provided. The secondary battery includes the electrode involved in the second embodiment as the negative electrode. In other words, the secondary battery involved in the third embodiment includes the electrode containing the active material involved in the first embodiment as the negative electrode.
[0150] The secondary battery according to the embodiment may further include a separator disposed between the positive electrode and the negative electrode. The negative electrode, the positive electrode, and the separator may constitute an electrode group. The electrolyte may be retained in the electrode group.
[0151] The secondary battery may further include an outer packaging member for housing the electrode group and the electrolyte.
[0152] In addition, the secondary battery may further include a negative electrode terminal electrically connected to the negative electrode and a positive electrode terminal electrically connected to the positive electrode.
[0153] The secondary battery may be, for example, a lithium ion secondary battery. Alternatively, the secondary battery may be a nonaqueous electrolyte secondary battery containing a nonaqueous electrolyte.
[0154] Hereinafter, the negative electrode, the positive electrode, the electrolyte, the separator, the outer casing member, the negative electrode terminal, and the positive electrode terminal are described in detail.
[0155] (1) Negative electrode
[0156] The negative electrode may include a negative electrode current collector and a negative electrode active material containing layer. The negative electrode current collector and the negative electrode active material containing layer may be the current collector and the active material containing layer that the electrode involved in the second embodiment can include, respectively. The negative electrode active material containing layer contains the active material involved in the first embodiment as the negative electrode active material.
[0157] The details of the negative electrode that overlap with those described in the second embodiment will be omitted.
[0158] The density of the negative electrode active material layer (excluding the current collector), i.e., the electrode density, is preferably 1.8 g / cm 3 Above and 3.5g / cm 3 The negative electrode energy density and electrolyte retention are excellent when the density of the negative electrode active material layer is within this range. The density of the negative electrode active material layer is more preferably 2.5 g / cm 3 Above and 2.9g / cm 3 the following.
[0159] The negative electrode can be produced, for example, by the same method as the electrode according to the second embodiment.
[0160] (2) Positive electrode
[0161] The positive electrode may include a positive electrode current collector and a positive electrode active material-containing layer. The positive electrode active material-containing layer may be formed on one side or both sides of the positive electrode current collector. The positive electrode active material-containing layer may include a positive electrode active material and any conductive agent and binder.
[0162] As the positive electrode active material, for example, an oxide or a sulfide can be used. The positive electrode can contain one compound alone as the positive electrode active material, or can contain two or more compounds in combination. As examples of oxides and sulfides, compounds that can embed and de-embed Li or Li ions can be cited.
[0163] Examples of such compounds include manganese dioxide (MnO2), iron oxide, copper oxide, nickel oxide, lithium manganese composite oxide (e.g., Li x Mn2O4 or Li x MnO2, 0<x≤1), lithium nickel composite oxide (such as Li x NiO2, 0<x≤1), lithium cobalt composite oxide (such as Li x CoO2, 0<x≤1), lithium nickel cobalt composite oxide (such as Li x Ni 1-y Co y O2, 0<x≤1, 0<y<1), lithium manganese cobalt composite oxide (such as Li x Mn y Co 1-yO2, 0<x≤1, 0<y<1), lithium manganese nickel composite oxide with spinel structure (such as Li x Mn 2-y Ni y O4, 0<x≤1, 0<y<2), lithium phosphorus oxide with olivine structure (such as Li x FePO4, 0<x≤1, Li x Fe 1-y Mn y PO4, 0<x≤1, 0<y<1, Li x CoPO4, 0<x≤1), iron sulfate (Fe2(SO4)3), vanadium oxide (such as V2O5) and lithium nickel cobalt manganese composite oxide (Li x Ni 1-y-z Co y Mn z O2, 0<x≤1, 0<y<1, 0<z<1, y+z<1).
[0164] Among the above, examples of more preferred compounds as positive electrode active materials include: lithium manganese composite oxides having a spinel structure (e.g., Li x Mn2O4, 0<x≤1), lithium nickel composite oxide (such as Li x NiO2, 0<x≤1), lithium cobalt composite oxide (such as Li x CoO2, 0<x≤1), lithium nickel cobalt composite oxide (such as Li x Ni 1-y Co y O2, 0<x≤1, 0<y<1), lithium manganese nickel composite oxide with spinel structure (such as Li x Mn 2-y Ni y O4, 0<x≤1, 0<y<2), lithium manganese cobalt composite oxide (such as Li x Mn y Co 1-y O2, 0<x≤1, 0<y<1), lithium iron phosphate (such as Li x FePO4, 0<x≤1) and lithium nickel cobalt manganese composite oxide (Li x Ni 1-y-z Co y Mn z O2, 0<x≤1, 0<y<1, 0<z<1, y+z<1). If these compounds are used in the positive electrode active material, the positive electrode potential can be improved.
[0165] When a room temperature molten salt is used as the electrolyte of the battery, it is preferred to use a mixture containing lithium iron phosphate, Li xPositive electrode active materials of VPO4F (0≤x≤1), lithium manganese composite oxide, lithium nickel composite oxide, lithium nickel cobalt composite oxide or mixtures thereof. These compounds can improve cycle life due to their low reactivity with room temperature molten salts. Details of room temperature molten salts will be described later.
[0166] The primary particle size of the positive electrode active material is preferably 100 nm or more and 1 μm or less. Positive electrode active materials with a primary particle size of 100 nm or more are easy to handle in industrial production. Positive electrode active materials with a primary particle size of 1 μm or less can smoothly diffuse lithium ions in the solid.
[0167] The specific surface area of the positive electrode active material is preferably 0.1 m 2 / g or more and 10m 2 / g or less. With 0.1m 2 / g or more of the positive electrode active material can fully secure the insertion and extraction sites of Li ions. 2 A positive electrode active material having a specific surface area of 100 Å / g or less is easy to handle in industrial production and can ensure good charge and discharge cycle performance.
[0168] The binder is used to fill the gaps between the dispersed positive electrode active materials and to bind the positive electrode active materials to the positive electrode current collector. Examples of binders include polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVdF), fluorine rubber, polyacrylic acid compounds, imide compounds, carboxymethyl cellulose (CMC) and salts of CMC. One of these can be used as a binder, or two or more of them can be used in combination as a binder.
[0169] The conductive agent is added to improve the current collection performance and suppress the contact resistance between the positive electrode active material and the positive electrode collector. Examples of conductive agents include carbon black such as vapor grown carbon fiber (VGCF), acetylene black, and carbonaceous materials such as graphite. One of them can be used as the conductive agent, or two or more of them can be used in combination as the conductive agent. In addition, the conductive agent can be omitted.
[0170] In the positive electrode active material containing layer, the positive electrode active material and the binder are preferably blended in a ratio of 80 mass % to 98 mass % and 2 mass % to 20 mass %, respectively.
[0171] By making the amount of the binder more than 2% by mass, sufficient electrode strength can be obtained. In addition, the binder can function as an insulator. Therefore, if the amount of the binder is less than 20% by mass, the internal resistance can be reduced due to the reduction in the amount of the insulator contained in the electrode.
[0172] When a conductive agent is added, the positive electrode active material, the binder and the conductive agent are preferably blended in a ratio of 77 mass % to 95 mass %, 2 mass % to 20 mass % and 3 mass % to 15 mass %, respectively.
[0173] By making the amount of the conductive agent more than 3% by mass, the above-mentioned effect can be exerted. In addition, by making the amount of the conductive agent less than 15% by mass, the proportion of the conductive agent in contact with the electrolyte can be reduced. If this proportion is low, the decomposition of the electrolyte can be reduced under high temperature storage.
[0174] The positive electrode current collector is preferably an aluminum foil or an aluminum alloy foil containing one or more elements selected from Mg, Ti, Zn, Ni, Cr, Mn, Fe, Cu and Si.
[0175] The thickness of the aluminum foil or aluminum alloy foil is preferably 5 μm or more and 20 μm or less, more preferably 15 μm or less. The purity of the aluminum foil is preferably 99% by mass or more. The content of transition metals such as iron, copper, nickel and chromium contained in the aluminum foil or aluminum alloy foil is preferably 1% by mass or less.
[0176] Furthermore, the positive electrode current collector may include a portion on the surface of which the positive electrode active material-containing layer is not formed. This portion may function as a positive electrode current collector tab.
[0177] The positive electrode can be produced, for example, by using a positive electrode active material in the same method as that of the electrode according to the second embodiment.
[0178] (3) Electrolytes
[0179] As the electrolyte, for example, a liquid nonaqueous electrolyte or a gel nonaqueous electrolyte can be used. The liquid nonaqueous electrolyte can be prepared by dissolving an electrolyte salt as a solute in an organic solvent. The concentration of the electrolyte salt is preferably 0.5 mol / L or more and 2.5 mol / L or less.
[0180] Examples of electrolyte salts include lithium salts such as lithium perchlorate (LiClO4), lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium hexafluoroarsenate (LiAsF6), lithium trifluoromethanesulfonate (LiCF3SO3) and bistrifluoromethanesulfonyl imide (LiN(CF3SO2)2) and mixtures thereof. As electrolyte salts, preferably, those that are difficult to oxidize even at high potentials are preferred, and LiPF6 is most preferred.
[0181] Examples of organic solvents include cyclic carbonates such as propylene carbonate (PC), ethylene carbonate (EC), and vinylene carbonate (VC); chain carbonates such as diethyl carbonate (DEC), dimethyl carbonate (DMC), and methylethyl carbonate (MEC); cyclic ethers such as tetrahydrofuran (THF), 2-methyltetrahydrofuran (2MeTHF), and dioxolane (DOX); chain ethers such as dimethoxyethane (DME) and diethoxyethane (DEE); γ-butyrolactone (GBL), acetonitrile (AN), and sulfolane (SL). These organic solvents may be used alone or as a mixed solvent.
[0182] The gel nonaqueous electrolyte can be prepared by compounding a liquid nonaqueous electrolyte with a polymer material. Examples of the polymer material include polyvinylidene fluoride (PVdF), polyacrylonitrile (PAN), polyethylene oxide (PEO), or a mixture thereof.
[0183] Alternatively, as the nonaqueous electrolyte, besides a liquid nonaqueous electrolyte and a gel nonaqueous electrolyte, a room-temperature molten salt (ionic melt) containing lithium ions, a polymer solid electrolyte, an inorganic solid electrolyte, or the like may be used.
[0184] As a room temperature molten salt (ionic melt), it refers to a compound that can exist as a liquid at room temperature (15°C to 25°C) in an organic salt formed by a combination of an organic cation and an anion. Room temperature molten salts include room temperature molten salts that exist as liquids in the form of monomers, room temperature molten salts that become liquids by mixing with electrolyte salts, room temperature molten salts that become liquids by dissolving in organic solvents, or mixtures of these room temperature molten salts. Generally speaking, the melting point of the room temperature molten salts used in secondary batteries is below 25°C. In addition, organic cations usually have a quaternary ammonium skeleton.
[0185] A polymer solid electrolyte can be prepared by dissolving an electrolyte salt in a polymer material and solidifying it.
[0186] The inorganic solid electrolyte is a solid substance having Li ion conductivity.
[0187] The electrolyte may be an aqueous electrolyte containing water.
[0188] The aqueous electrolyte contains an aqueous solvent and an electrolyte salt. The aqueous electrolyte is, for example, in liquid form. The liquid aqueous electrolyte is an aqueous solution prepared by dissolving an electrolyte salt as a solute in an aqueous solvent. The aqueous solvent is, for example, a solvent containing 50% by volume or more of water. The aqueous solvent may also be pure water.
[0189] The aqueous electrolyte may be a gel-like aqueous electrolyte obtained by combining an aqueous electrolyte solution with a polymer material. Examples of the polymer material include polyvinylidene fluoride (PVdF), polyacrylonitrile (PAN), and polyethylene oxide (PEO).
[0190] The aqueous electrolyte preferably contains 1 mol or more of the aqueous solvent per mol of the salt serving as the solute, and more preferably contains 3.5 mol or more of the aqueous solvent per mol of the salt serving as the solute.
[0191] The presence of water in an aqueous electrolyte can be confirmed by GC-MS (Gas Chromatography-Mass Spectrometry). In addition, the salt concentration and water content in an aqueous electrolyte can be determined, for example, by ICP (Inductively Coupled Plasma) luminescence analysis. By weighing a specified amount of an aqueous electrolyte and calculating the salt concentration contained, the molar concentration (mol / L) can be calculated. In addition, by measuring the specific gravity of the aqueous electrolyte, the number of moles of the solute and solvent can be calculated.
[0192] The aqueous electrolyte can be prepared by, for example, dissolving an electrolyte salt in an aqueous solvent at a concentration of 1 to 12 mol / L.
[0193] In order to suppress the electrolysis of the aqueous electrolyte, the pH may be adjusted by adding LiOH or Li2SO4, etc. The pH is preferably 3-13, more preferably 4-12.
[0194] (4) Diaphragm
[0195] The separator can be formed of, for example, a porous film or a synthetic resin nonwoven fabric containing polyethylene (PE), polypropylene (PP), cellulose or polyvinylidene fluoride (PVdF). From the perspective of safety, it is preferred to use a porous film formed of polyethylene or polypropylene. This is because these porous films melt at a certain temperature and can cut off the current.
[0196] As a diaphragm, a solid electrolyte layer containing solid electrolyte particles can also be used. The solid electrolyte layer can contain one solid electrolyte particle or multiple solid electrolyte particles. The solid electrolyte layer can also be a solid electrolyte composite membrane containing solid electrolyte particles. The solid electrolyte composite membrane is, for example, formed by molding solid electrolyte particles into a film shape using a polymer material. The solid electrolyte layer can also contain at least one selected from a plasticizer and an electrolyte salt. If the solid electrolyte layer contains an electrolyte salt, for example, the alkali metal ion conductivity of the solid electrolyte layer can be further improved.
[0197] Examples of polymer materials include polyether-based, polyester-based, polyamine-based, polyethylene-based, silicone-based, and polysulfide-based polymers.
[0198] As a solid electrolyte, an inorganic solid electrolyte is preferably used. As an inorganic solid electrolyte, for example, an oxide-based solid electrolyte or a sulfide-based solid electrolyte can be cited. As an oxide-based solid electrolyte, a lithium phosphate solid electrolyte having a NASICON-type structure and represented by the general formula LiM2(PO4)3 is preferably used. M in the above general formula is preferably selected from at least one element selected from titanium (Ti), germanium (Ge), strontium (Sr), zirconium (Zr), tin (Sn), and aluminum (Al). More preferably, the element M contains any one of Ge, Zr, and Ti and Al.
[0199] As a specific example of lithium phosphate solid electrolyte having a NASICON structure, LATP (Li 1+ x Al x Ti 2-x (PO4)3)、Li 1+x Al x Ge 2-x (PO4)3、Li 1+x Al x Zr 2-x (PO4)3. In the above formula, x is in the range of 0<x≤5, preferably in the range of 0.1≤x≤0.5. As the solid electrolyte, LATP is preferably used. LATP has excellent water resistance and is unlikely to be hydrolyzed in the secondary battery.
[0200] In addition, as an oxide-based solid electrolyte, amorphous LIPON (Li 2.9 PO 3.3 N 0.46 ) or garnet-type LLZ (Li7La3Zr2O 12 ).
[0201] (5) Outer packaging components
[0202] As the outer packaging member, for example, a container formed of a laminated film or a metal container can be used.
[0203] The thickness of the laminate film is, for example, 0.5 mm or less, or preferably 0.2 mm or less.
[0204] As the laminated film, a multilayer film including a plurality of resin layers and a metal layer sandwiched between the resin layers can be used. The resin layer contains, for example, a polymer material such as polypropylene (PP), polyethylene (PE), nylon, and polyethylene terephthalate (PET). The metal layer is preferably formed of aluminum foil or aluminum alloy foil for light weight. The laminated film can be sealed by hot melt bonding and molded into the shape of an outer packaging member.
[0205] The thickness of the metal container is, for example, preferably 1 mm or less, more preferably 0.5 mm or less, and even more preferably 0.2 mm or less.
[0206] The metal container can be made of, for example, aluminum or an aluminum alloy. Preferably, the aluminum alloy contains elements such as magnesium, zinc, and silicon. When the aluminum alloy contains transition metals such as iron, copper, nickel, and chromium, the content thereof is preferably 100 mass ppm or less.
[0207] The shape of the outer packaging member is not particularly limited. The shape of the outer packaging member may be, for example, flat (thin), square, cylindrical, coin-shaped, or button-shaped. The outer packaging member may be appropriately selected according to the battery size and the purpose of the battery.
[0208] (6) Negative terminal
[0209] The negative terminal can be formed of a material that is electrochemically stable and conductive at the Li insertion and extraction potential of the above-mentioned negative electrode active material. Specifically, as the material of the negative terminal, copper, nickel, stainless steel or aluminum, or an aluminum alloy containing at least one element selected from Mg, Ti, Zn, Mn, Fe, Cu and Si can be cited. As the material of the negative terminal, aluminum or an aluminum alloy is preferably used. The negative terminal is preferably formed of the same material as the negative electrode collector in order to reduce the contact resistance with the negative electrode collector.
[0210] (7) Positive terminal
[0211] The positive terminal can be formed by a potential range of 3V or more and 5V or less relative to the redox potential of lithium (vs. Li / Li + ) is formed of a material that is electrically stable and conductive. Examples of the material of the positive terminal include aluminum or an aluminum alloy containing at least one element selected from Mg, Ti, Zn, Mn, Fe, Cu, and Si. The positive terminal is preferably formed of the same material as the positive current collector in order to reduce the contact resistance with the positive electrode collector.
[0212] Next, a secondary battery according to a third embodiment will be described in more detail with reference to the drawings.
[0213] Figure 4 It is a cross-sectional view schematically showing an example of a secondary battery according to a third embodiment. Figure 5 yes Figure 4 An enlarged cross-sectional view of portion A of the secondary battery shown.
[0214] Figure 4 and Figure 5 The secondary battery 100 shown has: Figure 4 and Figure 5 The bag-shaped outer packaging member 2 shown, Figure 4 The electrode group 1 shown and the electrolyte (not shown) are accommodated in a bag-shaped outer packaging member 2. The electrolyte (not shown) is retained in the electrode group 1.
[0215] The bag-like outer package member 2 is formed of a laminated film including two resin layers and a metal layer sandwiched therebetween.
[0216] like Figure 4 As shown in FIG. 1 , the electrode group 1 is a flat wound electrode group. Figure 5 As shown, the negative electrode 3, the separator 4 and the positive electrode 5 are included. The separator 4 is interposed between the negative electrode 3 and the positive electrode 5.
[0217] The negative electrode 3 includes a negative electrode current collector 3a and a negative electrode active material layer 3b. Figure 5 As shown, the negative electrode active material containing layer 3b is formed only on the inner surface side of the negative electrode current collector 3a. In the other parts of the negative electrode 3, the negative electrode active material containing layer 3b is formed on both surfaces of the negative electrode current collector 3a.
[0218] The positive electrode 5 includes a positive electrode current collector 5 a and positive electrode active material-containing layers 5 b formed on both surfaces thereof.
[0219] like Figure 4As shown, the negative terminal 6 and the positive terminal 7 are located near the outer peripheral end of the wound electrode group 1. The negative terminal 6 is connected to the outermost portion of the negative electrode collector 3a. In addition, the positive terminal 7 is connected to the outermost portion of the positive electrode collector 5a. These negative terminals 6 and positive terminals 7 extend to the outside from the opening of the bag-like outer packaging member 2. A thermoplastic resin layer is provided on the inner surface of the bag-like outer packaging member 2, and the opening is sealed by heat-melting bonding.
[0220] The secondary battery according to the third embodiment is not limited to Figure 4 and Figure 5 The secondary battery of the structure shown may also be, for example Figure 6 and Figure 7 A battery having the structure shown.
[0221] Figure 6 It is a partially cutaway perspective view schematically showing another example of the secondary battery according to the third embodiment. Figure 7 yes Figure 6 An enlarged cross-sectional view of portion B of the secondary battery shown.
[0222] Figure 6 and Figure 7 The secondary battery 100 shown has Figure 6 and Figure 7 The electrode group 1 shown, Figure 6 The outer packaging member 2 is shown, and the electrolyte is not shown. The electrode group 1 and the electrolyte are accommodated in the outer packaging member 2. The electrolyte is retained in the electrode group 1.
[0223] The outer package member 2 is formed of a laminated film including two resin layers and a metal layer sandwiched therebetween.
[0224] Electrode group 1 Figure 7 The stacked electrode group 1 has a structure in which negative electrodes 3 and positive electrodes 5 are alternately stacked with separators 4 interposed therebetween.
[0225] The electrode group 1 includes a plurality of negative electrodes 3. Each of the plurality of negative electrodes 3 includes a negative electrode current collector 3a and a negative electrode active material-containing layer 3b supported on both surfaces of the negative electrode current collector 3a. In addition, the electrode group 1 includes a plurality of positive electrodes 5. Each of the plurality of positive electrodes 5 includes a positive electrode current collector 5a and a positive electrode active material-containing layer 5b supported on both surfaces of the positive electrode current collector 5a.
[0226] The negative electrode current collector 3a of each negative electrode 3 has a portion 3c on one side thereof which does not carry the negative electrode active material layer 3b on any surface. This portion 3c functions as a negative electrode current collector lug. Figure 7As shown, the portion 3c functioning as the negative electrode collector tab does not overlap with the positive electrode 5. In addition, the plurality of negative electrode collector tabs (portion 3c) are electrically connected to the strip-shaped negative electrode terminal 6. The front end of the strip-shaped negative electrode terminal 6 is led out of the outer packaging member 2.
[0227] In addition, although not shown, the positive electrode current collector 5a of each positive electrode 5 has a portion on one side thereof that does not carry the positive electrode active material layer 5b on any surface. This portion acts as a positive electrode collector ear. The positive electrode collector ear does not overlap with the negative electrode 3 in the same manner as the negative electrode collector ear (portion 3c). In addition, the positive electrode collector ear is located on the opposite side of the electrode group 1 relative to the negative electrode collector ear (portion 3c). The positive electrode collector ear is electrically connected to the strip-shaped positive terminal 7. The front end of the strip-shaped positive terminal 7 is located on the opposite side of the negative terminal 6 and is led out to the outside of the outer packaging member 2.
[0228] The secondary battery according to the third embodiment contains the active material according to the first embodiment as a negative electrode active material. Therefore, the secondary battery can exhibit excellent input-output characteristics and cycle life characteristics.
[0229] (Fourth embodiment)
[0230] According to a fourth embodiment, there is provided a battery pack. The battery pack according to the fourth embodiment includes a plurality of secondary batteries according to the third embodiment.
[0231] In the assembled battery according to the fourth embodiment, the individual cells may be arranged by being electrically connected in series or in parallel, or may be arranged by combining series connection and parallel connection.
[0232] Next, an example of a battery assembly according to a fourth embodiment will be described with reference to the drawings.
[0233] Figure 8 It is a perspective view schematically showing an example of a battery assembly according to a fourth embodiment. Figure 8 The illustrated assembled battery 200 includes five cells 100 a to 100 e , four bus bars 21 , a positive electrode lead 22 , and a negative electrode lead 23 . The five cells 100 a to 100 e are each a secondary battery according to the third embodiment.
[0234] The bus bar 21 connects, for example, the negative terminal 6 of one cell 100a and the positive terminal 7 of the adjacent cell 100b. In this way, five cells 100 are connected in series via four bus bars 21. That is, Figure 8The assembled battery 200 is a battery assembly of five connected in series. Although not shown in the figure, in an assembled battery including a plurality of cells electrically connected in parallel, the plurality of cells can be electrically connected by, for example, connecting a plurality of negative terminals with a bus bar and connecting a plurality of positive terminals with a bus bar.
[0235] The positive electrode terminal 7 of at least one of the five cells 100a to 100e is electrically connected to the positive electrode lead 22 for external connection. The negative electrode terminal 6 of at least one of the five cells 100a to 100e is electrically connected to the negative electrode lead 23 for external connection.
[0236] The assembled battery according to the fourth embodiment includes the secondary battery according to the third embodiment. Therefore, the assembled battery can exhibit excellent input-output characteristics and cycle-life characteristics.
[0237] (Fifth embodiment)
[0238] According to a fifth embodiment, a battery pack is provided. The battery pack includes the assembled battery according to the fourth embodiment. The battery pack may include a single secondary battery according to the third embodiment instead of the assembled battery according to the fourth embodiment.
[0239] The battery pack according to the fifth embodiment may further include a protection circuit. The protection circuit has a function of controlling the charge and discharge of the secondary battery. Alternatively, a circuit included in a device (such as an electronic device, a car, etc.) that uses the battery pack as a power source may be used as the protection circuit of the battery pack.
[0240] In addition, the battery pack involved in the fifth embodiment may further include an external terminal for power supply. The external terminal for power supply is used to output the current from the secondary battery to the outside and / or input the current from the outside to the secondary battery. In other words, when the battery pack is used as a power source, the current is supplied to the outside through the external terminal for power supply. In addition, when charging the battery pack, the charging current (including the regenerative energy of the power of the car, etc.) is supplied to the battery pack through the external terminal for power supply.
[0241] Next, an example of a battery pack according to a fifth embodiment will be described with reference to the drawings.
[0242] Fig. 9 It is an exploded perspective view schematically showing an example of a battery pack according to a fifth embodiment. Fig.10 Yes means Fig. 9 A block diagram of an example of a circuit of a battery pack is shown.
[0243] Fig. 9 and Fig.10The battery pack 300 shown includes a storage container 31 , a cover 32 , a protective sheet 33 , a battery module 200 , a printed wiring board 34 , wirings 35 , and an insulating plate (not shown).
[0244] Fig. 9 The storage container 31 shown is a bottomed square container having a rectangular bottom surface. The storage container 31 is configured to store a protective sheet 33, a battery pack 200, a printed wiring substrate 34, and wiring 35. The cover 32 has a rectangular shape. The cover 32 covers the storage container 31 to store the battery pack 200 and the like. Although not shown in the figure, the storage container 31 and the cover 32 are provided with an opening or a connection terminal for connection with an external device and the like.
[0245] The assembled battery 200 includes a plurality of unit cells 100 , a positive electrode lead 22 , a negative electrode lead 23 , and an adhesive tape 24 .
[0246] At least one of the plurality of cells 100 is a secondary battery according to the third embodiment. Fig.10 The plurality of cells 100 may be electrically connected in parallel, or may be connected in a combination of series connection and parallel connection. If the plurality of cells 100 are connected in parallel, the battery capacity is increased compared to when they are connected in series.
[0247] The adhesive tape 24 bundles the plurality of cells 100. A heat shrink tape may be used instead of the adhesive tape 24 to fix the plurality of cells 100. In this case, the protective sheet 33 is disposed on both sides of the battery pack 200, and after the heat shrink tape is wrapped around, the heat shrink tape is thermally shrunk to bundle the plurality of cells 100.
[0248] One end of the positive electrode lead 22 is connected to the assembled battery 200. One end of the positive electrode lead 22 is electrically connected to the positive electrode of one or more cells 100. One end of the negative electrode lead 23 is connected to the assembled battery 200. One end of the negative electrode lead 23 is electrically connected to the negative electrode of one or more cells 100.
[0249] The printed wiring board 34 is provided on a surface along one short side of the inner side surface of the storage container 31. The printed wiring board 34 includes a positive electrode side connector 342, a negative electrode side connector 343, a thermistor 345, a protection circuit 346, wirings 342a and 343a, an external terminal 350 for power supply, a positive electrode side wiring (positive side wiring) 348a, and a negative electrode side wiring (negative side wiring) 348b. One main surface of the printed wiring board 34 faces one side surface of the battery pack 200. An insulating plate (not shown) is sandwiched between the printed wiring board 34 and the battery pack 200.
[0250] The other end 22 a of the positive electrode lead 22 is electrically connected to the positive electrode connector 342 . The other end 23 a of the negative electrode lead 23 is electrically connected to the negative electrode connector 343 .
[0251] The thermistor 345 is fixed to one main surface of the printed wiring board 34. The thermistor 345 detects the temperature of each unit cell 100 and sends the detection signal to the protection circuit 346.
[0252] The external terminals 350 for power supply are fixed to the other main surface of the printed wiring board 34. The external terminals 350 for power supply are electrically connected to a device existing outside the battery pack 300. The external terminals 350 for power supply include a positive terminal 352 and a negative terminal 353.
[0253] The protection circuit 346 is fixed to the other main surface of the printed wiring substrate 34. The protection circuit 346 is connected to the positive terminal 352 via the positive side wiring 348a. The protection circuit 346 is connected to the negative terminal 353 via the negative side wiring 348b. In addition, the protection circuit 346 is electrically connected to the positive side connector 342 via the wiring 342a. The protection circuit 346 is electrically connected to the negative side connector 343 via the wiring 343a. In addition, the protection circuit 346 is electrically connected to the plurality of cells 100 via the wiring 35.
[0254] The protection sheet 33 is disposed on both inner side surfaces in the longitudinal direction of the storage container 31 and on the inner side surface in the transverse direction facing the printed wiring board 34 via the battery module 200. The protection sheet 33 is formed of, for example, resin or rubber.
[0255] The protection circuit 346 controls the charge and discharge of the plurality of cells 100. In addition, based on a detection signal sent from the thermistor 345 or a detection signal sent from each cell 100 or the assembled battery 200, the protection circuit 346 blocks the electrical connection between the protection circuit 346 and the external terminal 350 (positive terminal 352, negative terminal 353) for powering an external device.
[0256] As the detection signal sent from the thermistor 345, for example, a signal for detecting that the temperature of the single cell 100 has reached a predetermined temperature or higher can be cited. As the detection signal sent from each single cell 100 or the assembled battery 200, for example, a signal for detecting overcharge, overdischarge, and overcurrent of the single cell 100 can be cited. When detecting overcharge, etc. of each single cell 100, the battery voltage can be detected, or the positive electrode potential or the negative electrode potential can be detected. In the latter case, a lithium electrode used as a reference electrode is inserted into each single cell 100.
[0257] Alternatively, as the protection circuit 346 , a circuit included in a device (eg, electronic equipment, automobile, etc.) that uses the battery pack 300 as a power source may be used.
[0258] Furthermore, as described above, the battery pack 300 is provided with the external terminal 350 for power supply. Therefore, the battery pack 300 can output the current from the assembled battery 200 to the external device via the external terminal 350 for power supply, and can input the current from the external device to the assembled battery 200. In other words, when the battery pack 300 is used as a power source, the current from the assembled battery 200 can be supplied to the external device through the external terminal 350 for power supply. Furthermore, when charging the battery pack 300, the charging current from the external device can be supplied to the battery pack 300 through the external terminal 350 for power supply. When the battery pack 300 is used as a vehicle-mounted battery, the regenerative energy of the power of the vehicle can be used as the charging current from the external device.
[0259] In addition, the battery pack 300 may also include a plurality of battery assemblies 200. In this case, the plurality of battery assemblies 200 may be connected in series, in parallel, or in a combination of series connection and parallel connection. In addition, the printed wiring substrate 34 and the wiring 35 may be omitted. In this case, the positive electrode side lead 22 and the negative electrode side lead 23 may be used as the positive side terminal and the negative side terminal of the external terminal for power supply, respectively.
[0260] Such a battery pack can be used, for example, for applications requiring excellent cycle performance when a large current is taken out. Specifically, the battery pack can be used, for example, as a power source for electronic equipment, a stationary battery, or a vehicle-mounted battery for various vehicles. Examples of electronic equipment include digital cameras. The battery pack is particularly suitable for use as a vehicle-mounted battery.
[0261] The battery pack according to the fifth embodiment includes the secondary battery according to the third embodiment or the assembled battery according to the fourth embodiment. Therefore, the battery pack can exhibit excellent input-output characteristics and cycle-life characteristics.
[0262] (Sixth Implementation Method)
[0263] According to a sixth embodiment, there is provided a vehicle having the battery pack according to the fifth embodiment mounted thereon.
[0264] In the vehicle according to the sixth embodiment, the battery pack can recover regenerative energy of the power of the vehicle, for example. The vehicle may include a mechanism for converting the kinetic energy of the vehicle into regenerative energy.
[0265] Examples of the vehicle according to the sixth embodiment include a two-wheeled to four-wheeled hybrid electric vehicle, a two-wheeled to four-wheeled electric vehicle, an assist bicycle, and a railway vehicle.
[0266] The location where the battery pack is mounted in the vehicle is not particularly limited. For example, when the battery pack is mounted in a car, the battery pack may be mounted in the engine room of the vehicle, behind the vehicle body, or under a seat.
[0267] The vehicle may also be equipped with multiple battery packs. In this case, the batteries contained in each battery pack may be electrically connected to each other in series, in parallel, or in a combination of series connection and parallel connection. For example, when each battery pack contains a battery pack, the battery packs may be electrically connected to each other in series, in parallel, or in a combination of series connection and parallel connection. Alternatively, when each battery pack contains a single battery, the batteries may be electrically connected to each other in series, in parallel, or in a combination of series connection and parallel connection.
[0268] Next, an example of a vehicle according to a sixth embodiment will be described with reference to the drawings.
[0269] Fig.11 This is a partial perspective view schematically showing an example of a vehicle according to the embodiment.
[0270] Fig.11 The vehicle 400 shown includes a vehicle body 40 and a battery pack 300 according to the embodiment. Fig.11 In the example shown, the vehicle 400 is a four-wheeled automobile.
[0271] The vehicle 400 may also be equipped with a plurality of battery packs 300. In this case, the batteries (eg, single batteries or battery packs) included in the battery pack 300 may be connected in series, in parallel, or in a combination of series connection and parallel connection.
[0272] Fig.11 The middle figure shows an example in which the battery pack 300 is mounted in the engine room located in front of the vehicle body 40. As described above, the battery pack 300 may be mounted, for example, behind the vehicle body 40 or under a seat. The battery pack 300 can be used as a power source for the vehicle 400. In addition, the battery pack 300 can recover the regenerative energy of the power of the vehicle 400.
[0273] Next, refer to Fig.12 An embodiment of a vehicle according to a sixth embodiment will be described.
[0274] Fig.12 This is a diagram schematically showing an example of a control system related to an electrical system in a vehicle according to a sixth embodiment. Fig.12 The illustrated vehicle 400 is an electric vehicle.
[0275] Fig.12 The vehicle 400 shown includes a vehicle body 40 , a vehicle power supply 41 , a vehicle ECU (Electric Control Unit) 42 which is a higher-level control device of the vehicle power supply 41 , an external terminal (a terminal for connecting to an external power supply) 43 , an inverter 44 , and a drive motor 45 .
[0276] The vehicle 400 has a vehicle power source 41 mounted in, for example, an engine room, a rear part of a vehicle body, or under a seat. Fig.12 In the illustrated vehicle 400 , a mounting location of a vehicle power supply 41 is schematically shown.
[0277] The vehicle power supply 41 includes a plurality of (eg, three) battery packs 300 a , 300 b , and 300 c , a battery management unit (BMU) 411 , and a communication bus 412 .
[0278] The battery pack 300a includes a battery pack 200a and a battery pack monitoring device 301a (e.g., VTM: Voltage Temperature Monitoring). The battery pack 300b includes a battery pack 200b and a battery pack monitoring device 301b. The battery pack 300c includes a battery pack 200c and a battery pack monitoring device 301c. The battery packs 300a to 300c are the same battery packs as the above-mentioned battery pack 300, and the battery packs 200a to 200c are the same battery packs as the above-mentioned battery pack 200. The battery packs 200a to 200c are electrically connected in series. The battery packs 300a, 300b, and 300c can be independently removed and exchanged with other battery packs 300.
[0279] Each of the assembled batteries 200a to 200c includes a plurality of cells connected in series. At least one of the plurality of cells is a secondary battery according to the third embodiment. Each of the assembled batteries 200a to 200c is charged and discharged via a positive electrode terminal 413 and a negative electrode terminal 414.
[0280] The battery management device 411 communicates with the assembled battery monitoring devices 301a to 301c to collect information on voltage, temperature, etc. of each cell 100 included in the assembled batteries 200a to 200c included in the vehicle power supply 41. Thus, the battery management device 411 collects information on maintenance of the vehicle power supply 41.
[0281] The battery management device 411 and the assembled battery monitoring devices 301a to 301c are connected via a communication bus 412. In the communication bus 412, a plurality of nodes (the battery management device 411 and one or more assembled battery monitoring devices 301a to 301c) share a set of communication lines. The communication bus 412 is, for example, a communication bus configured based on the CAN (Control Area Network) standard.
[0282] The assembled battery monitoring devices 301a to 301c measure the voltage and temperature of each cell constituting the assembled batteries 200a to 200c based on a command via communication from the battery management device 411. However, the temperature may be measured at only a few locations in one assembled battery, and the temperature of all cells may not be measured.
[0283] The vehicle power supply 41 may further include an electromagnetic contactor (eg, Fig.12 The switch device 415 is shown in FIG. 4 . The switch device 415 includes a pre-charge switch (not shown) that is turned on when charging the assembled batteries 200a to 200c and a main switch (not shown) that is turned on when the output from the assembled batteries 200a to 200c is supplied to a load. The pre-charge switch and the main switch each include a relay circuit (not shown) that is turned on or off based on a signal supplied to a coil disposed near the switch element. The electromagnetic contactor such as the switch device 415 is controlled based on a control signal from the vehicle ECU 42 that controls the operation of the battery management device 411 or the entire vehicle 400.
[0284] The inverter 44 converts the input DC voltage into a high voltage of three-phase alternating current (AC) for driving the motor. The three-phase output terminals of the inverter 44 are connected to the three-phase input terminals of the drive motor 45. The inverter 44 is controlled based on a control signal from the vehicle ECU 42 that controls the battery management device 411 or the overall operation of the vehicle. The output voltage from the inverter 44 is adjusted by controlling the inverter 44.
[0285] The drive motor 45 is rotated by the electric power supplied from the inverter 44. The driving force generated by the rotation of the drive motor 45 is transmitted to the axle and the drive wheel W through, for example, a differential gear unit.
[0286] In addition, although not shown, the vehicle 400 is provided with a regenerative braking mechanism (regenerator). The regenerative braking mechanism rotates the drive motor 45 when braking the vehicle 400, converting kinetic energy into regenerative energy as electrical energy. The regenerative energy recovered by the regenerative braking mechanism is input to the inverter 44 and converted into a direct current. The converted direct current is input to the vehicle power supply 41.
[0287] One terminal of the connection line L1 is connected to the negative terminal 414 of the vehicle power supply 41. The other terminal of the connection line L1 is connected to the negative input terminal 417 of the inverter 44. On the connection line L1, a current detection unit (current detection circuit) 416 in the battery management device 411 is provided between the negative terminal 414 and the negative input terminal 417.
[0288] One terminal of the connection line L2 is connected to the positive terminal 413 of the vehicle power supply 41. The other terminal of the connection line L2 is connected to the positive input terminal 418 of the inverter 44. A switch device 415 is provided between the positive terminal 413 and the positive input terminal 418 on the connection line L2.
[0289] The external terminal 43 is connected to the battery management device 411. The external terminal 43 can be connected to an external power source, for example.
[0290] The vehicle ECU 42 controls the vehicle power supply 41, the switch device 415, the inverter 44, etc. in coordination with other management devices and control devices including the battery management device 411 in response to the operation input of the driver, etc. The vehicle ECU 42 controls the output of the power from the vehicle power supply 41 and the charging of the vehicle power supply 41, etc., and manages the entire vehicle 400. Data related to the maintenance of the vehicle power supply 41, such as the remaining capacity of the vehicle power supply 41, is transmitted between the battery management device 411 and the vehicle ECU 42 through the communication line.
[0291] The vehicle according to the sixth embodiment is equipped with the battery pack according to the fifth embodiment. Therefore, according to this embodiment, it is possible to provide a vehicle equipped with a battery pack that can exhibit excellent input-output characteristics and cycle-life characteristics.
[0292] [Example]
[0293] Hereinafter, the above-mentioned embodiment will be described in more detail based on examples.
[0294] <Synthesis method>
[0295] (Example 1)
[0296] The active material was synthesized by the solid phase synthesis method described below.
[0297] First, in order to obtain Nb2TiO7 as the main phase and Nb 10 TiO 29, Nb2O5 particles and TiO2 particles were mixed in a dry ball mill at a molar ratio of 1.1:1 in such a way that the Nb / Ti ratio reached 2.2. The obtained powder was placed in an alumina crucible, and after being heated at a temperature of 800°C for 10 hours, it was crushed and mixed, and then temporarily calcined again at a temperature of 800°C for 10 hours (first calcination) to obtain precursor particles. Then, the obtained precursor particles were formally calcined at 1000°C for 5 hours (second calcination). The particle size distribution of the particles obtained after the formal calcination was investigated, and the results showed that D10 was greater than 0.3μm and D90 was less than 10μm.
[0298] Next, potassium carbonate (K2CO3) and diammonium hydrogen phosphate ((NH4)2HPO4) are added to the particles after formal firing in such a manner that the concentrations of potassium (K) and phosphorus (P) in the final active material particles reach 0.01 mass % and 0.001 mass %, respectively. The particles after formal firing to which the K source and the P source have been added are subjected to wet mixing using pure water to obtain a wet mixture. Then, the wet mixture is subjected to annealing treatment to improve the crystallinity. The annealing treatment is performed at 900°C for 3 hours. The powder thus obtained is crushed at 500 rpm for 10 minutes using an agate ball mill using a pulverizing medium with a diameter of 10 mm to obtain the active material powder involved in Example 1.
[0299] (Examples 2 to 10)
[0300] Active material powders according to Examples 2 to 10 were obtained in the same manner as in Example 1 except that the amounts of K source and P source added were changed so as to obtain active materials having potassium concentrations and phosphorus concentrations shown in Table 1 below for the particles after main calcination.
[0301] (Example 11)
[0302] An active material powder was obtained in the same manner as in Example 4 except that an annealing treatment was performed at 800° C. for 1 hour.
[0303] (Example 12)
[0304] An active material powder was obtained in the same manner as in Example 4 except that an annealing treatment was performed at 800° C. for 3 hours.
[0305] (Example 13)
[0306] An active material powder was obtained in the same manner as in Example 4 except that an annealing treatment was performed at 900° C. for 5 hours.
[0307] (Example 14)
[0308] An active material powder was obtained in the same manner as in Example 4 except that an annealing treatment was performed at 900° C. for 10 hours.
[0309] (Example 15)
[0310] The active material powder was obtained in the same manner as in Example 4, except that when mixing the raw materials of the Nb source and the Ti source, the Nb / Ti ratio was achieved to be 2.02, and the Nb2O5 particles and the TiO2 particles were mixed in a dry ball mill at a molar ratio of 1.01:1.
[0311] (Example 16)
[0312] The active material powder was obtained in the same manner as in Example 4, except that when mixing the raw materials of the Nb source and the Ti source, the Nb / Ti ratio was achieved to be 2.1, and the Nb2O5 particles and the TiO2 particles were mixed in a dry ball mill at a molar ratio of 1.05:1.
[0313] (Example 17)
[0314] The active material powder was obtained in the same manner as in Example 4, except that when mixing the raw materials of the Nb source and the Ti source, the Nb / Ti ratio was achieved to be 3.0, and the Nb2O5 particles and the TiO2 particles were mixed in a dry ball mill at a molar ratio of 1.5:1.
[0315] (Example 18)
[0316] The active material powder was obtained in the same manner as in Example 4, except that when mixing the raw materials of the Nb source and the Ti source, the Nb / Ti ratio was set to 3.5, and the Nb2O5 particles and the TiO2 particles were mixed in a dry ball mill at a molar ratio of 1.75:1.
[0317] (Example 19)
[0318] The active material powder was obtained in the same manner as in Example 4, except that when mixing the raw materials of the Nb source and the Ti source, the Nb2O5 particles and the TiO2 particles were mixed in a molar ratio of 2:1 using a dry ball mill so that the Nb / Ti ratio reached 4.0.
[0319] (Example 20)
[0320] After the annealed powder was obtained by the method of Example 14, it was not pulverized by an agate ball mill, but was sieved to remove coarse grains of 10 μm or more. In this way, an active material powder with a reduced specific surface area was obtained.
[0321] (Example 21)
[0322] After obtaining the annealed powder by the method of Example 11, the powder was pulverized by an agate ball mill with a pulverizing medium of 10 mm in diameter at 600 rpm for 30 minutes. Then, microparticles of 0.3 μm or less were removed by centrifugal separation. In this way, active material particles with increased specific surface area were obtained.
[0323] (Example 22)
[0324] After obtaining the annealed powder by the method of Example 11, the powder was pulverized by an agate ball mill with a pulverizing medium of 10 mm in diameter at 800 rpm for 40 minutes. Then, microparticles of 0.3 μm or less were removed by centrifugal separation. In this way, active material particles with an increased specific surface area were obtained.
[0325] (Example 23)
[0326] The active material powder was obtained by the same method as in Example 17 except that the mixing using an agate mortar was performed instead of the mixing using a dry ball mill when mixing the raw materials of the Nb source and the Ti source. By performing gentle mixing using an agate mortar instead of dry mixing that applies a strong shear force like a ball mill, a solid phase reaction of niobium enrichment proceeds locally, thereby generating Nb as a coexisting phase. 14 TiO 37 .
[0327] (Example 24)
[0328] The active material powder was obtained by the same method as in Example 19 except that the mixing using an agate mortar was performed instead of the mixing using a dry ball mill when mixing the raw materials of the Nb source and the Ti source. By performing gentle mixing using an agate mortar instead of dry mixing that applies a strong shear force like a ball mill, a solid phase reaction of niobium enrichment proceeds locally, thereby generating Nb as a coexisting phase. 24 TiO 64 .
[0329] (Comparative Example 1)
[0330] Active material powder was obtained in the same manner as in Example 1 except that only potassium carbonate (K2CO3) was added to the particles after the main firing so that the potassium (K) concentration in the finally obtained active material particles would be 0.07 mass %.
[0331] (Comparative Example 2)
[0332] Active material powder was obtained in the same manner as in Example 1 except that only diammonium hydrogen phosphate ((NH4)2HPO4) was added to the particles after the main firing so that the phosphorus (P) concentration in the final active material particles would be 0.009 mass %.
[0333] (Comparative Example 3)
[0334] The active material powder is obtained in the same manner as in Example 1, except that potassium carbonate (K2CO3) and diammonium hydrogen phosphate ((NH4)2HPO4) are added to the particles after formal sintering so that the concentrations of potassium (K) and phosphorus (P) in the final active material particles reach 5.0 mass % and 2.0 mass %, respectively.
[0335] (Comparative Example 4)
[0336] An active material powder was obtained in the same manner as in Example 1 except that wet mixing with pure water was performed without adding a K source or a P source.
[0337] (Comparative Example 5)
[0338] The active material powder is obtained in the same manner as in Example 1, except that sodium carbonate (Na2CO3) and ferric chloride (FeCl2) are added to the particles after formal firing in such a way that the concentrations of sodium (Na) and iron (Fe) in the active material particles finally obtained reach 0.05 mass %, instead of adding the K source and the P source.
[0339] (Comparative Example 6)
[0340] The powder obtained after annealing according to the method of Example 14 was used as the active material powder of Comparative Example 6. That is, in Comparative Example 6, the pulverization process was not performed after the annealing process.
[0341] (Comparative Example 7)
[0342] After obtaining the annealed powder by the method of Example 4, the powder was pulverized by a dry bead mill using a pulverizing medium with a diameter of 3 mm at a pass frequency of 3 times to obtain an active material powder.
[0343] (Comparative Example 8)
[0344] The active material powder was obtained in the same manner as in Example 4, except that when mixing the raw materials of the Nb source and the Ti source, the Nb2O5 particles and the TiO2 particles were mixed in a molar ratio of 1:1 so that the Nb / Ti ratio reached 2.00 in order to obtain only the Nb2TiO7 phase.
[0345] (Comparative Example 9)
[0346] An active material powder according to Comparative Example 9 was prepared in the same manner as in Example 1 except that the following operations were performed.
[0347] When mixing the raw materials of the Nb source and the Ti source, in order to obtain only the Nb2TiO7 phase, the molar ratio of the Nb2O5 particles and the TiO2 particles was set to 1:1 so that the Nb / Ti ratio reached 2.00. In addition, when adding the K source and the P source, potassium carbonate (K2CO3) and diammonium hydrogen phosphate ((NH4)2HPO4) were added to the particles after the formal firing so that the concentrations of potassium (K) and phosphorus (P) in the active material particles finally obtained reached 5.0 mass% and 2.0 mass%, respectively.
[0348] (Comparative Example 10)
[0349] The active material powder was obtained in the same manner as in Example 4, except that when mixing the raw materials of the Nb source and the Ti source, the Nb / Ti ratio was set to 4.5, and the Nb2O5 particles and the TiO2 particles were mixed in a dry ball mill at a molar ratio of 2.25:1.
[0350] (Comparative Example 11)
[0351] First, in order to obtain Nb2TiO7 as the main phase and Nb 10 TiO 29 , using a dry ball mill, Nb2O5 particles and TiO2 particles were mixed at a molar ratio of 1.1:1 in such a way that the Nb / Ti ratio reached 2.2. The obtained powder was placed in an alumina crucible, heated at 800°C for 10 hours, crushed and mixed, and then temporarily calcined at 800°C for 10 hours (first calcination) to obtain precursor particles.
[0352] Next, potassium carbonate (K2CO3) and diammonium hydrogen phosphate ((NH4)2HPO4) are added to the precursor particles so that the concentrations of potassium (K) and phosphorus (P) in the final active material particles reach 0.07 mass % and 0.009 mass %, respectively. The precursor particles to which the K source and the P source are added are subjected to wet mixing using pure water to obtain a wet mixture.
[0353] Next, the obtained wet mixture was subjected to main calcination (second calcination) at 1150° C. for 3 hours. The powder thus obtained was pulverized at 500 rpm for 30 minutes using an agate ball mill using a pulverizing medium with a diameter of 10 mm to obtain an active material powder according to Comparative Example 11.
[0354] (Comparative Example 12)
[0355] First, in order to obtain the Nb2TiO7 phase as the main phase, Nb2O5 particles and TiO2 particles were mixed in a dry ball mill at a molar ratio of 1:1. The obtained powder was placed in an alumina crucible and temporarily calcined at 800°C for 12 hours. The powder obtained after the temporary calcination was placed in a platinum crucible and formally calcined at 1200°C for 5 hours. After the powder was crushed in an agate mortar, it was sieved with a 25μm mesh to obtain Nb2TiO7 particles.
[0356] Next, in order to obtain Nb as a secondary phase 10 TiO 29 The Nb2O5 particles and the TiO2 particles were prepared by temporarily firing, firing and screening in the same manner as in the preparation of the main phase, except that the molar ratio of the Nb2O5 particles to the TiO2 particles was set to 2.5:1, to obtain Nb 10 TiO 29 Particles. The obtained Nb 10 TiO 29 The particles were mixed with the previously prepared Nb2TiO7 particles in such a way that the content of the particles reached 0.5% by mass to obtain a mixture.
[0357] Potassium carbonate (K2CO3) and diammonium hydrogen phosphate ((NH4)2HPO4) were added so that the concentrations of potassium (K) and phosphorus (P) in the active material particles finally obtained were 0.01 mass % and 0.001 mass %, respectively, relative to the obtained mixture. The mixture to which the K source and the P source were added was subjected to wet mixing using pure water to obtain a wet mixture. Then, the wet mixture was subjected to annealing treatment at 900°C for 3 hours.
[0358] The powder thus obtained was pulverized using an agate ball mill using a pulverizing medium having a diameter of 10 mm at 500 rpm for 10 minutes, thereby obtaining an active material powder according to Comparative Example 12.
[0359] <Electrochemical Measurement>
[0360] Using the active material obtained in each example, a cell for electrochemical measurement was produced in the following manner.
[0361] 100% by mass of the active material powder obtained in each example, 10% by mass of acetylene black as a conductive agent and 5% by mass of carbon nanofibers, and 10% by mass of polyvinylidene fluoride (PVdF) as a binder were added to N-methylpyrrolidone (NMP) and mixed to obtain a slurry. The slurry was applied to one side of a current collector formed of an aluminum foil with a thickness of 12 μm, dried, and pressed to produce an electrode with a density of 2.4 g / cm 3 of electrodes.
[0362] On the other hand, an electrolyte solution was prepared by dissolving a LiPF6 supporting salt at a concentration of 1 mol / L in a mixed solvent of ethylene carbonate (EC) and diethyl carbonate (DEC) at a volume ratio of 1:2.
[0363] The obtained electrode was used as a working electrode, and Li metal was used as a counter electrode and a reference electrode. A three-electrode beaker cell using an electrolyte solution was prepared, and electrochemical characteristics were evaluated as described below.
[0364] In this embodiment, in the three-electrode beaker battery used for the measurement, since lithium metal is used as the counter electrode and the electrode potential of the embodiment and the comparative example is expensive compared to the counter electrode, it works as a positive electrode. Therefore, the definition of charging and discharging when the electrode of the embodiment and the comparative example is used as the negative electrode is opposite. Here, in order to avoid confusion, in this embodiment, the direction in which lithium ions are embedded in the electrode is uniformly referred to as charging, and the direction in which lithium ions are extracted is referred to as discharging. In addition, the active material of this embodiment works as a negative electrode by combining with a known positive electrode material.
[0365] The prepared battery for electrochemical measurements was charged and discharged in the potential range of 1.0V to 3.0V based on the metal lithium electrode. The charge and discharge current value was set to 0.2C (hourly discharge rate), and the 0.2C discharge capacity was confirmed at room temperature. The value of the 0.2C discharge capacity is an indicator of energy density. In addition, in order to investigate the rapid discharge characteristics, after confirming the 0.2C discharge capacity, the charging current value was set to 0.2C again for charging, and the 5C rapid discharge capacity was confirmed at room temperature. Then, by dividing the 5C discharge capacity by the 0.2C discharge capacity, the discharge capacity ratio (5C / 0.2C) was calculated. The discharge capacity ratio (5C / 0.2C) is an indicator for evaluating rapid charge and discharge characteristics.
[0366] Next, in order to confirm that the active material (negative electrode material) involved in the embodiment can be stably charged and discharged, the battery of the embodiment and the comparative example was subjected to a life test of repeated 0.2C charge and discharge in a potential range of 1.0V to 3.0V and at 45°C based on the metal lithium electrode. At the end of the initial charge and discharge stage, the AC impedance value of the battery at 1kHz was measured. Then, 100 cycles of repeated charge and discharge (charging and discharging as 1 cycle) were performed, and the discharge capacity retention rate and resistance increase rate after 100 cycles were investigated. In order to confirm the discharge capacity retention rate after 100 cycles, charge and discharge were performed again at 0.2C (hourly discharge rate), and the discharge capacity after 100 cycles was divided by the initial discharge capacity, and then multiplied by 100, thereby calculating the cycle capacity retention rate (%) when the initial discharge capacity was set to 100%. In addition, the AC impedance value at 1kHz was measured after 100 cycles, and it was divided by the AC impedance value after the initial charge and discharge to calculate the resistance increase rate (times). The discharge capacity maintenance rate and resistance increase rate after 100 cycles are indicators for evaluating cycle life characteristics.
[0367] <Various Reviews>
[0368] The active material powder obtained in each example was subjected to powder X-ray diffraction, Rietveld analysis, ICP emission spectroscopy, TEM observation, specific surface area measurement by the BET method, and laser diffraction scattering according to the method described in the first embodiment.
[0369] The above results are summarized in the following Tables 1 to 4. In the row of Comparative Example 5, the sodium concentration is described in the "K / Concentration" column instead of the potassium concentration. Also, the iron concentration is described in the "P / Concentration" column instead of the phosphorus concentration.
[0370]
[0371]
[0372]
[0373]
[0374] As shown in Examples 1 to 24, the secondary battery containing the active material according to the embodiment is excellent not only in input-output characteristics and cycle life characteristics, but also in battery capacity. K and phosphorus concentration C P The ratio (C K / C P) is within the range of 2.0 to 50.0, the effect of crystal growth and the effect of inhibiting grain growth can be well balanced, and the battery characteristics are excellent by smoothly performing the electrochemical reaction in the electrode. The rate characteristics and cycle life characteristics of Examples 12 and 13, in which D10 is 0.4 μm or more and D90 is 9.0 μm or less, are well balanced and excellent.
[0375] As in Comparative Example 4, if potassium and phosphorus are omitted, the reactivity is low even if annealing is performed because the melting point does not drop. Therefore, active material particles containing unreacted impurity phases and having a small crystallite size are obtained. As in Comparative Example 5, when a predetermined amount of sodium and iron are contained, the melting point drops and the particle properties are the same as those of the example, but the influence of the deterioration of battery characteristics caused by sodium and iron is greater.
[0376] In Comparative Example 6, the D90 was too large due to insufficient crushing of the particles, so that the electron conduction path was not sufficiently formed, and the battery characteristics were poor. On the other hand, in Comparative Example 7, the active material powder was crushed excessively, so the crystallinity decreased, the specific surface area increased, and the cycle life characteristics were very poor.
[0377] As shown in Comparative Example 8, when the Nb-rich phase is not included, the stability of the lattice during charge and discharge decreases, resulting in poor battery characteristics. On the other hand, if the Nb-rich phase is large, as shown in Comparative Example 10, the effect of excessively strengthening the bonding between oxide ions and Nb ions constituting the skeleton is achieved, thereby hindering the movement of lithium ions and resulting in poor battery characteristics.
[0378] As in Comparative Example 11, crystal growth is promoted by calcining a mixture containing potassium and phosphorus at a specified concentration for a long time at a high temperature, but grain growth is also promoted at the same time. Therefore, coarse particles that are difficult to crush are generated. If a powder containing such coarse particles is crushed with a ball mill, the amount of fine powder produced when the coarse particles are crushed increases. Therefore, D10 is as small as a value of 0.18μm, and D90 also reaches more than 10μm due to a large amount of residual coarse grains. Therefore, the rate characteristics and cycle life characteristics are reduced, and the resistance after the cycle increases significantly. Due to the large number of coarse grains and fine powders, the reaction in the electrode is uneven, so the rate characteristics decrease. In addition, the coarse grains can collapse through changes in the lattice volume, so the electronic conductive network in the electrode is destroyed. In addition, due to the presence of microparticles, the side reactions with the electrolyte are also increased, so the resistance increases significantly.
[0379] In Comparative Example 12, since both when the Nb2TiO7 phase as the main phase is generated and when the Nb 10 TiO 29During the phase generation, sintering is continuously performed at high temperature, so niobium-titanium composite oxide particles with high hardness are already generated before the addition of K source and P source. Therefore, if the main phase and the sub-phase are mixed and potassium and phosphorus are added at a predetermined concentration and then heated, high-strength particles that are difficult to crush even with a ball mill are generated. Therefore, the rate characteristics are very low, and the high-strength particles slowly split during the charge and discharge cycle, resulting in an increase in resistance and a decrease in capacity.
[0380] According to at least one embodiment and example described above, an active material can be provided. The active material contains a Nb2TiO7 phase and a phase selected from Nb 10 TiO 29 Phase, Nb 14 TiO 37 Phase and Nb 24 TiO 64 At least one Nb-rich phase in the phase. The active material contains potassium and phosphorus, and the total concentration of potassium and phosphorus in the active material is in the range of 0.01 mass % to 5.00 mass %. The average particle size is in the range of 80nm to 150nm. In the particle size distribution diagram obtained by laser diffraction scattering method, D10 is greater than 0.3μm and D90 is less than 10μm. The active material satisfies the peak intensity ratio expressed by the following formula (1).
[0381] 0<I B / I A ≤0.25 (1)
[0382] In formula (1), I A It is the peak intensity of the maximum peak attributable to the Nb2TiO7 phase that appears at 26.0±0.1° in the diffraction peaks obtained by wide-angle X-ray diffraction using CuKα rays as the X-ray source. B It is the peak intensity of the maximum peak attributable to the Nb-rich phase that appears at 2θ of 24.9±0.2° among the diffraction peaks.
[0383] This active material can realize a secondary battery that can show excellent input-output characteristics and cycle life characteristics.
[0384] In addition, the above-mentioned implementation modes can be summarized into the following technical solutions.
[0385] Technical Solution 1
[0386] An active material comprising a Nb2TiO7 phase and a 10 TiO 29 Phase, Nb 14 TiO 37 Phase and Nb 24 TiO 64At least one Nb-rich phase in the active material,
[0387] It contains potassium and phosphorus.
[0388] The total concentration of the potassium and the phosphorus in the active material is within a range of 0.010 mass % to 5.00 mass %,
[0389] In the particle size distribution diagram obtained by the laser diffraction scattering method, D10 is 0.3 μm or more, D90 is 10 μm or less,
[0390] The average crystallite size is in the range of 80nm to 150nm.
[0391] The active material satisfies the peak intensity ratio represented by the following formula (1).
[0392] 0<I B / I A ≤0.25 (1)
[0393] In the formula (1), I A is the peak intensity of the maximum peak attributable to the Nb2TiO7 phase appearing at 26.0±0.1° in the diffraction peaks obtained by wide-angle X-ray diffraction using CuKα rays as the X-ray source, I B It is the peak intensity of the maximum peak attributable to the Nb-rich phase appearing at 2θ of 24.9±0.2° among the diffraction peaks.
[0394] Technical Solution 2
[0395] According to the above technical solution 1,
[0396] The potassium concentration C in the active substance K and the phosphorus concentration C in the active material P The ratio (C K / C P ) is in the range of 2.0 to 50.0.
[0397] Technical Solution 3
[0398] According to the above technical solution 1 or 2,
[0399] The total concentration of the potassium and the phosphorus in the active material is within a range of 0.050 mass % to 2.50 mass %.
[0400] Technical Solution 4
[0401] According to any one of the above technical solutions 1 to 3,
[0402] The average crystallite diameter is greater than 90 nm.
[0403] Technical Solution 5
[0404] According to any one of the above technical solutions 1 to 4,
[0405] BET specific surface area is 0.5m 2 / g or more and 5m 2 / g or less.
[0406] Technical Solution 6
[0407] According to any one of the above technical solutions 1 to 5,
[0408] In the particle size distribution diagram, D10 is 0.4 μm or more.
[0409] Technical Solution 7
[0410] According to any one of the above technical solutions 1 to 6,
[0411] In the particle size distribution diagram, D90 is 9.0 μm or less.
[0412] Technical Solution 8
[0413] According to any one of the above technical solutions 1 to 7,
[0414] The peak intensity ratio I B / I A In the range of 0.005 or more and 0.20 or less.
[0415] Technical Solution 9
[0416] An electrode comprising the active material according to any one of technical solutions 1 to 8 above.
[0417] Technical Solution 10
[0418] According to the above technical solution 9,
[0419] The electrode includes an active material-containing layer containing the active material.
[0420] Technical Solution 11
[0421] A secondary battery comprising a positive electrode, a negative electrode and an electrolyte, wherein:
[0422] The negative electrode is the electrode described in the above technical solution 9 or 10.
[0423] Technical Solution 12
[0424] A battery pack comprises the secondary battery described in technical solution 11 above.
[0425] Technical Solution 13
[0426] According to the above technical solution 12, it further comprises:
[0427] External terminals for power supply, and
[0428] Protection circuit.
[0429] Technical Solution 14
[0430] According to the above technical solution 12 or 13,
[0431] The device comprises a plurality of the secondary batteries, and the secondary batteries are electrically connected in series, in parallel, or in a combination of series and parallel.
[0432] Technical Solution 15
[0433] A vehicle equipped with a battery pack according to any one of the above technical solutions 12 to 14.
[0434] Technical Solution 16
[0435] According to the above technical solution 15,
[0436] It has a mechanism for converting the kinetic energy of the vehicle into regenerative energy.
[0437] Several embodiments of the present invention have been described, but these embodiments are presented as examples and are not intended to limit the scope of the invention. These novel embodiments can be implemented in various other ways, and various omissions, substitutions, and changes can be made without departing from the scope of the subject matter of the invention. These embodiments and their variations are included in the scope and subject matter of the invention, and are also included in the invention described in the claims and their equivalents.
Claims
1. An active material comprising a Nb2TiO7 phase and a Nb 10 TiO 29 Phase, Nb 14 TiO 37 Phase and Nb 24 TiO 64 At least one Nb-rich phase in the active material, in, The active substance contains potassium and phosphorus, The total concentration of the potassium and the phosphorus in the active material is within a range of 0.010 mass % to 5.00 mass %, In the particle size distribution diagram obtained by the laser diffraction scattering method, D10 is 0.3 μm or more and 1.5 μm or less, and D90 is 10 μm or less, The average crystallite size calculated by Scherrer's formula is in the range of 80nm to 150nm. The phosphorus is present in at least a portion of the surface of the active material particle, and a portion of the phosphorus and a portion of the potassium are incorporated into a crystal phase.
2. The active material according to claim 1, wherein The potassium concentration C in the active substance K and the phosphorus concentration C in the active material P C K / C P In the range of 1.0 to 50.
0.
3. The active material according to claim 1, wherein The potassium concentration C in the active substance K and the phosphorus concentration C in the active material P C K / C P In the range of 2.0~50.
0.
4. The active material according to claim 1 or 2, wherein The total concentration of the potassium and the phosphorus in the active material is within a range of 0.050 mass % to 2.50 mass %.
5. The active material according to claim 1 or 2, wherein The average crystallite diameter is greater than 90 nm.
6. The active material according to claim 1 or 2, wherein BET specific surface area is 0.5m 2 / g or more and 5m 2 / g or less.
7. The active material according to claim 1 or 2, wherein In the particle size distribution diagram, D10 is 0.4 μm or more.
8. The active material according to claim 1 or 2, wherein In the particle size distribution diagram, D90 is 9.0 μm or less.
9. The active material according to claim 1 or 2, which satisfies the peak intensity ratio represented by the following formula (1): 0<I B / I A ≤0.25 (1) In the formula (1), I A is the peak intensity of the maximum peak attributable to the Nb2TiO7 phase appearing at 26.0±0.1° in the diffraction peaks obtained by wide-angle X-ray diffraction using CuKα rays as the X-ray source, I B It is the peak intensity of the maximum peak attributable to the Nb-rich phase appearing at 2θ of 24.9±0.2° among the diffraction peaks.
10. The active material according to claim 9, wherein The peak intensity ratio I B / I A In the range of 0.005 or more and 0.20 or less. 11 . An electrode comprising the active material according to claim 1 .
12. The electrode according to claim 11, wherein The electrode includes an active material-containing layer containing the active material.
13. A secondary battery comprising a positive electrode, a negative electrode and an electrolyte, wherein: The negative electrode is the electrode according to claim 11 or 12. 14 . A battery pack comprising the secondary battery according to claim 13 .
15. The battery pack according to claim 14, wherein: Further including: External terminals for power supply, and Protection circuit.
16. The battery pack according to claim 14 or 15, wherein: A plurality of the secondary batteries are provided, and the secondary batteries are electrically connected in series, in parallel, or in a combination of series and parallel.